Multiblock copolymers, photoresist compositions including the same, and pattern formation methods
By using multi-block copolymerized polymer in photoresist, the problems of linewidth roughness and process windows in high-resolution lithography are solved, and a higher resolution and a more reliable semiconductor manufacturing process is achieved.
Patent Information
- Application Number
- JP2024172452
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-10-04
- Filing Date
- 2024-10-01
- Publication Date
- 2025-04-16
AI Technical Summary
The prior art is difficult to effectively solve the linewidth roughness (LWR) and process window problems of photoresist during high-resolution lithography, especially in semiconductor manufacturing below крит。
Multi-block copolymerization polymer is used, specifically, the first and second blocks each contain multiple repeating units with different structures, and these repeating units include acid dissociable groups, lactic acid groups, salt groups, or hydroxybenzene groups. The repeating units of these blocks are structurally the same and ensure uniformity and high resolution performance of the photoresist through specific proportions and gradient structures.
By using multi-block copolymerized polymer, the resolution and linewidth roughness of the photoresist are significantly improved, the process window is expanded, thereby improving the integration density and yield reliability of semiconductor manufacturing.
Smart Images

Figure 2025063861000001 
Figure 2025063861000002 
Figure 2025063861000003
Abstract
Description
[Technical field]
[0001] FIELD OF THEINVENTION This invention relates to multi-block copolymers for photoresist compositions and patterning methods using such photoresist compositions.The present invention finds applicability in lithography applications in the semiconductor manufacturing industry. [Background technology]
[0002] Photoresist materials are photosensitive compositions typically used to transfer images to one or more underlying layers, such as metal, semiconductor, or dielectric layers, disposed on a semiconductor substrate. To increase the integration density of semiconductor devices and enable the formation of structures having dimensions in the nanometer range, photoresists and photolithography processing tools with high resolution capabilities have been and continue to be developed.
[0003] Modern lithography patterning processes currently use ArF (193 nm) immersion scanners to process wafers with dimensions below 60 nanometers (nm). Pushing ArF lithography to critical dimensions below 60 nm creates several challenges with photoresist capabilities in terms of process window, line width roughness (LWR) and other important parameters for high volume manufacturing of integrated circuits. All of these parameters must be addressed in next generation formulations. As feature dimensions decrease at advanced nodes, LWR values do not decrease at the same rate at the same time, resulting in a large source of variability in processing at those leading edge nodes. Process window improvements are also useful to achieve high yields in integrated circuit manufacturing.
[0004] Extreme ultraviolet lithography (EUV lithography) is another emerging technology for high volume semiconductor wafer manufacturing with critical dimensions below 20 nm.
[0005] Photoresist polymers are often used in photoresist compositions to achieve useful properties during photolithographic processing. However, when using polymers prepared by conventional methods, the uneven distribution of polymer functionality between polymer chains and / or variations along the polymer backbone can present problems when attempting to pattern at higher resolution. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] U.S. Patent No. 6,887,962 [Patent Document 2] US Patent Application Publication No. 2004 / 0180019 [Patent Document 3] U.S. Patent No. 8,431,325 [Patent Document 4] U.S. Pat. No. 4,189,323 Summary of the Invention [Problem to be solved by the invention]
[0007] There remains a continuing need for photoresist compositions to address one or more of the challenges associated with photolithographic patterning at critical dimensions below 60 nm, and in particular, there is a continuing need for photoresist compositions that can achieve improved resolution and reduced LWR. [Means for solving the problem]
[0008] One embodiment provides a block copolymer comprising a first block comprising two or more structurally distinct repeat units and a second block comprising two or more structurally distinct repeat units, wherein the repeat units of the first block comprise an acid labile group, a lactone group, a salt group or a hydroxyaryl group, and the repeat units of the second block comprise an acid labile group, a lactone group, a salt group or a hydroxyaryl group, and the two or more structurally distinct repeat units of the first block are the same as the two or more structurally distinct repeat units of the second block.
[0009] Another embodiment provides a polymer comprising one or more block copolymers described herein attached to another portion of the polymer.
[0010] Yet another aspect provides a photoresist composition comprising a block copolymer provided herein and a solvent.
[0011] Another aspect provides a method of forming a pattern, the method including forming a photoresist composition layer on a substrate from a photoresist composition, patternwise exposing the photoresist composition layer to activating radiation, and developing the exposed photoresist composition layer to provide a resist relief image. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Reference will now be made in detail to the exemplary embodiments, examples of which are illustrated in the present description. In this regard, the exemplary embodiments may have different forms and should not be construed as being limited to the description set forth herein. Accordingly, the exemplary embodiments are described below merely to illustrate aspects of the present description. As used herein, the term "and / or" includes any and all combinations of one or more of the associated listed items. A phrase such as "at least one of," when preceding a list of elements, modifies the entire list of elements and does not modify each individual element of the list.
[0013] As used herein, the terms "a," "an," and "the" do not denote quantity limitations and should be construed to include both the singular and the plural unless otherwise stated herein or clearly contradicted by context. "Or" means "and / or" unless otherwise stated. The modifier "about," used in connection with a quantity, is inclusive of the stated value and has the meaning dictated by the context (e.g., includes the degree of error associated with measurement of the particular quantity). All ranges disclosed herein are inclusive of the endpoints, which are independent and combinable with each other. The suffix "(s)" is intended to include both the singular and the plural of the term it modifies, thereby including at least one of that term. "Optional" or "optionally" means that the subsequently described event or circumstance may or may not occur, and that the description includes instances when the event occurs and instances when the event does not occur. The terms "first," "second," etc., as used herein do not denote an order, quantity, or importance, but rather are used to distinguish one element from another. When an element is said to be "on" another element, it may be in direct contact with the other element, or there may be intervening elements between them. In contrast, when an element is said to be "directly on" another element, there are no intervening elements present. It will be understood that the described components, elements, limitations and / or features of the embodiments may be combined in any suitable manner in the various embodiments.
[0014] Unless otherwise defined, all terms used herein (including technical and scientific terms) have the same meaning as commonly understood by those skilled in the art to which the present invention belongs. Terms such as those defined in commonly used dictionaries should be interpreted to have a meaning consistent with their meaning in the context of the relevant technical field and this disclosure, and will be further understood not to be interpreted in an ideal or overly formal sense unless expressly defined in this specification.
[0015] As used herein, "actinic rays" or "radiation" refers to, for example, the emission spectrum of a mercury lamp, far ultraviolet rays represented by an excimer laser, extreme ultraviolet rays (EUV light), X-rays, particle rays such as electron beams and ion beams, etc. Furthermore, in the present invention, "light" refers to actinic rays or radiation. Krypton fluoride lasers (KrF lasers) are a specific type of excimer laser that can be called exciplex lasers. "Excimer" stands for "excimer dimers", while "exciplex" stands for "excimer complexes". Excimer lasers use a mixture of rare gases (argon, krypton, or xenon) and halogen gases (fluorine or chlorine), which emits coherent stimulating radiation (laser light) in the ultraviolet range under suitable conditions of electrical stimulation and high pressure. Furthermore, unless otherwise specified, "exposure" in this specification includes not only exposure to far ultraviolet light represented by a mercury lamp or an excimer laser, X-rays, extreme ultraviolet light (EUV light), and the like, but also writing with particle beams such as electron beams and ion beams.
[0016] As used herein, the term "hydrocarbon" refers to an organic compound or group having at least one carbon atom and at least one hydrogen atom, "alkyl" refers to a straight or branched chain saturated hydrocarbon group having the specified number of carbon atoms and having a valence of one, "alkylene" refers to an alkyl group having a valence of two, "hydroxyalkyl" refers to an alkyl group substituted with at least one hydroxyl group (-OH), "alkoxy" refers to "alkyl-O-", and "carboxyl" refers to an alkyl group having a valence of two. and "carboxylic acid group" refers to a group having the formula "-C(=O)-OH", "cycloalkyl" refers to a monovalent group having one or more saturated rings in which all ring members are carbon, "cycloalkylene" refers to a cycloalkyl group having a valence of two, "alkenyl" refers to a linear or branched monovalent hydrocarbon group having at least one carbon-carbon double bond, "alkenoxy" refers to "alkenyl-O-", "alkenylene" refers to an alkenyl group having a valence of two, and "cycloalkenyl" refers to a monovalent hydrocarbon group having at least one carbon-carbon double bond. "aryl" refers to a non-aromatic cyclic divalent hydrocarbon group having at least three carbon atoms and having at least one carbon-carbon double bond; "alkynyl" refers to a monovalent hydrocarbon group having at least one carbon-carbon triple bond; the term "aromatic group" refers to a monocyclic or polycyclic aromatic ring system that satisfies the Hückel rule (4n+2 pi electrons) and contains carbon atoms in the ring; the term "heteroaromatic group" refers to an aromatic group that contains one or more heteroatoms (e.g., 1 to 4 heteroatoms) selected from N, O and S in place of carbon atoms in the ring; and "aryl" refers to a non-aromatic cyclic divalent hydrocarbon group having at least three carbon atoms and having at least one carbon-carbon double bond; "aryl" refers to a monovalent monocyclic or polycyclic aromatic ring system which may include groups in which all ring members are carbon and which have an aromatic ring fused to at least one cycloalkyl or heterocycloalkyl ring; "arylene" refers to an aryl group having a valence of two; "alkylaryl" refers to an aryl group substituted with an alkyl group; "arylalkyl" refers to an alkyl group substituted with an aryl group; "aryloxy" refers to "aryl-O-"; and "arylthio" refers to "aryl-S-".
[0017] The prefix "hetero" means that the compound or group contains at least one ring member that is a heteroatom (e.g., 1, 2, 3, or more heteroatoms) in place of a carbon atom, each heteroatom being independently N, O, S, Si, or P; a "heteroatom-containing group" refers to a substituent that contains at least one heteroatom; "heteroalkyl" refers to an alkyl group having at least one heteroatom in place of carbon; and "heterocycloalkyl" refers to a cycloalkyl group having 1 to 4 heteroatoms as ring members in place of carbon. "Heterocycloalkylene" refers to a heterocycloalkyl group having a valence of two, and "heteroaryl" refers to an aromatic 4-8 membered monocyclic, 8-12 membered bicyclic, or 11-14 membered tricyclic ring having 1-4 heteroatoms (in the case of a monocyclic ring), 1-6 heteroatoms (in the case of a bicyclic ring), or 1-9 heteroatoms (in the case of a tricyclic ring) each independently selected from N, O, S, Si, or P (e.g., carbon atoms and 1-3, 1-6, or 1-9 heteroatoms of N, O, or S, respectively, in the case of a monocyclic, bicyclic, or tricyclic ring, respectively). Examples of heteroaryl groups include pyridyl, furyl (furyl or furanyl), imidazolyl, benzimidazolyl, pyrimidinyl, thiophenyl or thienyl, quinolinyl, indolyl, thiazolyl, etc., and "heteroarylene" refers to a heteroaryl group having a valence of two.
[0018] The term "halogen" refers to a monovalent substituent that is fluorine (fluoro), chlorine (chloro), bromine (bromo), or iodine (iodo). The prefix "halo" refers to a group that contains one or more of fluoro, chloro, bromo, or iodo substituents in place of a hydrogen atom. A combination of halo groups (e.g., bromo and fluoro) or only fluoro groups can be present. For example, the term "haloalkyl" refers to an alkyl group substituted with one or more halogens. As used herein, "substituted C 1~8 "Haloalkyl" means a C substituted with at least one halogen. 1~8It refers to an alkyl group, which is further substituted with one or more other substituents that are not halogens. It is understood that substitution of a group with a halogen atom is not considered a heteroatom-containing group because a halogen atom does not replace a carbon atom.
[0019] Each of the foregoing substituents may be optionally substituted unless expressly specified otherwise. The term "optionally substituted" refers to substituted or unsubstituted. "Substituted" means that at least one hydrogen atom of a chemical structure or group is replaced with another terminal substituent, which is typically monovalent, provided that the normal valence of the designated atom is not exceeded. When the substituent is oxo (i.e., O), two geminal hydrogen atoms on the carbon atom are replaced with terminal oxo groups. It is further noted that the oxo group is bonded to the carbon through a double bond to form a carbonyl (C=O), and the carbonyl group is represented herein as -C(O)-. Combinations of substituents or variables are permitted. Exemplary substituents that may be present at the "substituted" position include nitro (-NO2), cyano (-CN), hydroxyl (-OH), oxo (O), amino (-NH2), mono- or di-(C 1~6 ) Alkylamino, alkanoyl (acyl, etc.) 2~6 alkanoyl group, etc.), formyl (-C(O)H), carboxylic acid or its alkali metal salt or ammonium salt;C 2~6 Alkyl esters (-C(O)O-alkyl or -OC(O)-alkyl) and C 7~13 Esters, such as aryl esters (-C(O)O-aryl or -OC(O)-aryl), including acrylates, methacrylates and lactones; amides (-C(O)NR, where R is hydrogen or C 1~6 alkyl), carboxamide (-CHC(O)NR, where R is hydrogen or C 1~6 alkyl), halogen, thiol (-SH), C 1~6 Alkylthio (-S-alkyl), thiocyano (-SCN), C 1~6 Alkyl, C 2~6 Alkenyl, C 2~6 Alkynyl, C 1~6Haloalkyl, C 1~9 Alkoxy, C 1~6 Haloalkoxy, C 3~12 Cycloalkyl, C 5~18 Cycloalkenyl, C 2~18 Heterocycloalkenyl, C having at least one aromatic ring 6~12 Aryl (e.g., phenyl, biphenyl, naphthyl, etc., each ring being substituted or unsubstituted aromatic), C having 1 to 3 separate or fused rings and 6 to 18 ring carbon atoms 7~19 Arylalkyl, arylalkoxy having 1-3 separate or fused rings and 6-18 ring carbon atoms, C 7~12 Alkylaryl, C 3~12 Heterocycloalkyl, C 3~12 Heteroaryl, C 1~6 Alkylsulfonyl (-S(O)2-alkyl), C 6~12 These include, but are not limited to, arylsulfonyl, (-S(O)2-aryl) or tosyl (CH3C6H4SO2-).
[0020] As used herein, unless otherwise defined, a "divalent linking group" and a "linking group" include -O-, -S-, -Te-, -Se-, -C(O)-, -C(O)O-, -N(R ’ )-, C(O)N(R ’ )-, -S(O)-, -S(O)2-, -C(S)-, -C(Te)-, -C(Se)-, substituted or unsubstituted C 1~30 Alkylene, substituted or unsubstituted C 3~30 Cycloalkylene, substituted or unsubstituted C 3~30 Heterocycloalkylene, substituted or unsubstituted C 6~30 Arylene, substituted or unsubstituted C 3~30 or combinations thereof, each R' is independently hydrogen, substituted or unsubstituted C 1~20 Alkyl, substituted or unsubstituted C 1~20 Heteroalkyl, substituted or unsubstituted C 6~30 Aryl or substituted or unsubstituted C 3~30Typically, the divalent linking group is -O-, -S-, -C(O)-, -C(O)O-, -N(R')-, C(O)N(R ’ )-, -S(O)-, -S(O)2-, substituted or unsubstituted C 1~30 Alkylene, substituted or unsubstituted C 3~30 Cycloalkylene, substituted or unsubstituted C 3~30 Heterocycloalkylene, substituted or unsubstituted C 6~30 Arylene, substituted or unsubstituted C 3~30 R' is one or more of hydrogen, substituted or unsubstituted C1-20 alkyl, substituted or unsubstituted C1-20 heteroalkyl, substituted or unsubstituted C6-30 aryl, or substituted or unsubstituted C 3~30 More typically, the divalent linking group includes -O-, -C(O)-, -C(O)O-, -N(R ’ )-, -C(O)N(R')-, substituted or unsubstituted C 1~10 Alkylene, substituted or unsubstituted C 3~10 Cycloalkylene, substituted or unsubstituted C 3~10 Heterocycloalkylene, substituted or unsubstituted C 6~10 Arylene, substituted or unsubstituted C 3~10 or a combination thereof, wherein R′ is hydrogen, substituted or unsubstituted C 1~10 Alkyl, substituted or unsubstituted C 1~10 Heteroalkyl, substituted or unsubstituted C 6~10 Aryl or substituted or unsubstituted C 3~10 It is heteroaryl.
[0021] As used herein, "acid labile group" refers to a group whose bond is cleaved by the action of an acid, optionally and typically with thermal treatment, resulting in the formation of a polar group, such as a carboxylic acid group or an alcohol group. In some cases, the acid labile group may be formed on a polymer, and optionally and typically the moiety attached to the cleaved bond is detached from the polymer. In other systems, a non-polymeric compound may contain an acid labile group that may be cleaved by the action of an acid, resulting in the formation of a polar group, such as a carboxylic acid group or an alcohol group, on the cleaved moiety of the non-polymeric compound. Such an acid is typically a photogenerated acid, where the bond cleavage occurs during post-exposure baking (PEB). However, the embodiments are not limited thereto, for example, such an acid may be thermally generated. Suitable acid labile groups include, for example, tertiary alkyl ester groups, secondary or tertiary aryl ester groups, secondary or tertiary ester groups with a combination of alkyl and aryl groups, tertiary alkoxy groups, acetal groups, or ketal groups. Acid labile groups are commonly referred to in the art as "acid cleavable groups", "acid cleavable protecting groups", "acid labile protecting groups", "acid leaving groups", "acid labile groups" and "acid sensitive groups".
[0022] The present invention relates to a multi-block copolymer that provides a solution to the compositional variation of polymers used for photoresist compositions. For example, when a polymer is prepared by free radical polymerization or manufactured using a controlled radical dump-and-run method, it often leads to compositional homogeneity problems between polymer chains or heterogeneity along the polymer backbone. In typical free radical or controlled radical copolymerization (or other chain copolymerization techniques), comonomers are randomly distributed along the polymer backbone or between different polymer chains due to differences in their incorporation rates. The present invention provides a multi-block copolymer in which the polymer chain breaks down into a small number of blocks, and two or more blocks can have the same specific composition of repeating units and optionally the same compositional gradient, so that the multi-block copolymer can provide a substantially uniform distribution of repeating units along the entire polymer backbone.
[0023] The use of multi-block structures allows the final polymer properties to be tailored based on the selection and gradient of monomers. For example, the properties obtained with conventional copolymers are typically an average of the properties imparted by the resulting monomers incorporated, whereas block copolymers lead to composite materials that contain unique properties inherent to each parent polymer block segment. Gradient structures using multi-block structures allow the tailoring of each block segment, simplifying the copolymer synthesis process. (Patent Document 1) and (Patent Document 2) show examples of gradient copolymers produced by controlled radical polymerization (CRP).
[0024] When a copolymer segment is synthesized using controlled radical polymerization (CRP) techniques, it is called a gradient copolymer. This type of copolymer is different from the copolymers obtained by conventional free radical processes, and the copolymer properties will depend on the monomer composition, the control agent used, and the polymerization conditions. For example, when a monomer mix is polymerized by conventional free radical polymerization, a statistical copolymer is produced. The polymers produced at each moment during the polymerization will not be the same in composition. Furthermore, due to the constant production of free radicals and the constantly changing monomer ratios throughout the reaction, the composition between different polymer chains will not be uniform. During CRP, the chains remain active throughout the polymerization, and therefore, the composition between different polymer chains will be uniform, but each chain will have a gradient in terms of composition. Thus, in a two monomer system where one monomer reacts faster than the other, the distribution or "profile" of the monomer units will be such that the concentration of one monomer unit is higher at one end of the block.
[0025] A block copolymer is provided that includes a first block that includes two or more structurally different repeat units and a second block that includes two or more structurally different repeat units. The repeat units of the first block include an acid labile group, a lactone group, a salt group, or a hydroxyaryl group, and the repeat units of the second block include an acid labile group, a lactone group, a salt group, or a hydroxyaryl group, and the two or more structurally different repeat units of the first block are the same as the two or more structurally different repeat units of the second block. For example, the first block and the second block can each include two structurally different repeat units, three structurally different repeat units, or four or more structurally different repeat units, provided that the first block and the second block have the same structurally different repeat units.
[0026] It should be noted that the block copolymer may optionally further comprise other blocks (i.e., third, fourth, fifth, etc.) that may be the same or different from the first and second blocks described herein. In some embodiments, the block copolymer may further comprise blocks that do not have the same structurally different repeat units as the first and second blocks. For example, the block copolymer may comprise a third block that comprises repeat units that may be different from the repeat units of the first and second blocks. In other embodiments, the block copolymer may comprise a third block that comprises repeat units that may be different from the repeat units of the first and second blocks, and a fourth block that may comprise repeat units that may be different from the repeat units of the first, second and third blocks. The additional blocks of the block copolymer may each comprise a single repeat unit, or the additional blocks of the block copolymer may each comprise two or more structurally different repeat units. In some embodiments, when the block copolymer includes additional blocks, the additional blocks may each include two or more structurally distinct repeat units, and the two or more structurally distinct repeat units may be different or the same between each additional block and for the first block and the second block.
[0027] In some embodiments, every block of the block copolymer can have two or more structurally different repeat units that are the same. In other words, in some embodiments, the block copolymer does not include an additional block or blocks that have polymerized units that are different from the repeat units in the first and second blocks.
[0028] The two or more structurally different repeat units of the first block and the two or more structurally different repeat units of the second block can be present in the first block and the second block in any suitable ratio, for example, the molar ratio of the two or more structurally different repeat units of the first block can be the same or different from the molar ratio of the two or more structurally different repeat units of the second block. For example, a block copolymer can have a first block of repeat units A and B and a second block of repeat units A and B, and the ratio of repeat units A to repeat units B in the first block can be the same or different from the ratio of repeat units A to repeat units B in the second block. If the block copolymer further comprises additional blocks in addition to the first block and the second block, each additional block can independently have structurally different repeat units in any suitable ratio.
[0029] In some embodiments, the two or more structurally different repeat units of the first block and the two or more structurally different repeat units of the second block may be present in the first block and the second block in substantially the same ratio, and each block has the same structural unit gradient direction from the first end to the second end of the block. For example, the two or more structurally different repeat units of the first block and the two or more structurally different repeat units of the second block may be present in the first block and the second block in substantially the same molar ratio based on the total moles of repeat units in the first block and the second block, respectively. As used herein, the term "structural unit gradient direction" may refer to a gradient based on the molar ratio of repeat units. In some embodiments, every block of the block copolymer may have the same two or more structurally different repeat units, and the two or more structurally different repeat units of each block may be present in substantially the same ratio, and each block has the same structural unit gradient direction from the first end to the second end of the block.
[0030] As noted above, the first block and the second block of the block copolymer include an acid labile group, a lactone group, a salt group, or a hydroxyaryl group. For example, in some embodiments, the first block and the second block may each include a repeat unit that includes an acid labile group. In some embodiments, the first block and the second block may each include a repeat unit that includes a lactone group or a salt group. For example, in some embodiments, the first block and the second block of the block copolymer may each include a first repeat unit that includes an acid labile group and a second repeat unit that includes a lactone group or a salt group.
[0031] In some embodiments, the first block and the second block of the block copolymer may each include a first repeat unit comprising an acid labile group and a second repeat unit comprising a lactone group. In yet other embodiments, the first block and the second block of the block copolymer may each include a first repeat unit comprising an acid labile group, a second repeat unit comprising a first lactone group, and a third repeat unit comprising a second lactone group, where the first and second lactone groups are different. In yet other embodiments, the first block and the second block of the block copolymer may each include a first repeat unit comprising a first acid labile group, a second repeat unit comprising a second acid labile group, and a third repeat unit comprising a lactone group, where the first and second acid labile groups are different.
[0032] Suitable acid labile groups include, for example, tertiary alkyl ester groups, secondary or tertiary aryl ester groups, secondary or tertiary ester groups with a combination of alkyl and aryl groups, tertiary alkoxy groups, acetal groups, ketal groups, tertiary carbonate groups, and tertiary carbamate groups.Typically, the acid labile group can be an acetal group, a ketal group, a tertiary carbonate group, a tertiary carbamate group, or a tertiary ester group.As used herein, "tertiary carbamate group" includes tertiary carbamate ester groups with alkyl groups, tertiary carbamate ester groups with aryl groups, and tertiary carbamate ester groups with a combination of alkyl and aryl groups.As used herein, "tertiary carbonate group" includes tertiary carbonate ester groups with alkyl groups, tertiary carbonate ester groups with aryl groups, and tertiary carbonate ester groups with a combination of alkyl and aryl groups.Preferably, the acid labile group includes a tertiary ester group.
[0033] The repeat units of the block copolymer may contain acid labile groups represented by one or more of formulas (1)-(5). [ka]
[0034] In formulas (1) to (3), each R a are independently hydrogen, fluorine, cyano, substituted or unsubstituted C 1~10 Alkyl or substituted or unsubstituted C 1~10 Fluoroalkyl. Preferably, R a is hydrogen, fluorine or substituted or unsubstituted C 1~5 It is an alkyl group, typically methyl.
[0035] In equation (1), L 1 is a divalent linking group. For example, L 1 can be a divalent linking group containing at least one carbon atom, at least one heteroatom, or a combination thereof. For example, L 1may contain 1 to 10 carbon atoms and at least one heteroatom. 1 is -OCH2-, -OCH2CH2O- or -N(R c )-(wherein, R c is hydrogen, substituted or unsubstituted C 1~10 Alkyl, substituted or unsubstituted C 1~10 Heteroalkyl, substituted or unsubstituted C 6~10 Aryl or substituted or unsubstituted C 3~10 Heteroaryl.
[0036] In equations (1), (2) and (4), R 1 ~R 3 are each independently hydrogen, substituted or unsubstituted C 1~20 Alkyl, substituted or unsubstituted C 3~20 Cycloalkyl, substituted or unsubstituted C 1~20 Heterocycloalkyl, substituted or unsubstituted C 2~20 Alkenyl, substituted or unsubstituted C 3~20 Cycloalkenyl, substituted or unsubstituted C 3~20 Heterocycloalkenyl, substituted or unsubstituted C 6~20 Aryl or substituted or unsubstituted C 2~20 heteroaryl, provided that R 1 ~R 3 can be hydrogen, and R 1 ~R 3 If one of is hydrogen, then R 1 ~R 3 The other one or both of are substituted or unsubstituted C 6~20 Aryl or substituted or unsubstituted C 4~20 Provided that R is heteroaryl. Preferably, R 1 ~R 3 are each independently a substituted or unsubstituted C 1~6 Alkyl or substituted or unsubstituted C 3~10 It is cycloalkyl.
[0037] In equations (1), (2) and (4), R 1 ~R 3any two of these optionally together form a ring; R 1 ~R 3 Each of the optionally includes as part of their structure -O-, -C(O)-, -N(R c )-, -S- or -S(O)2- (wherein R c is hydrogen, linear or branched C 1~20 Alkyl, monocyclic or polycyclic C 3~20 Cycloalkyl or monocyclic or polycyclic C 1~20 For example, R 1 ~R 3 any one or more of the formula -CHC(=O)CH (3-n) Y n wherein each Y is independently a substituted or unsubstituted C 1~30 heterocycloalkyl, where n is 1 or 2. For example, each Y can be independently a group of the formula -O(C a1 )(C a2 )O-(wherein, C a1 and C a2 are each independently hydrogen or a substituted or unsubstituted C 1~10 Alkyl, C a1 and C a2 may optionally form a ring) 1~30 It may be a heterocycloalkyl.
[0038] In equations (3) and (5), R 4 and R 5 are each independently hydrogen, substituted or unsubstituted C 1~20 Alkyl, substituted or unsubstituted C 3~20 Cycloalkyl, substituted or unsubstituted C 1~20 Heterocycloalkyl, substituted or unsubstituted C 6~20 Aryl or substituted or unsubstituted C 2~20 may be heteroaryl, R 6 is a substituted or unsubstituted C 1~20 Alkyl, substituted or unsubstituted C 3~20 Cycloalkyl or substituted or unsubstituted C 1~30Optionally, R can be heterocycloalkyl. 4 or R 5 One of them is R 6 and R may form a heterocycle together. 4 and R 5 are each independently hydrogen, substituted or unsubstituted C 1~20 Alkyl, substituted or unsubstituted C 3~20 Cycloalkyl or substituted or unsubstituted C 1~20 It may be a heterocycloalkyl.
[0039] In equations (4) and (5), L 2 and L 3 are each independently a single bond or a divalent linking group. 2 and L 3 are each independently a substituted or unsubstituted C 6~30 Arylene or substituted or unsubstituted C 3~30 For example, in some embodiments, L 3 does not contain a (meth)acrylate group as part of its structure.
[0040] In formulas (4) and (5), each of n1 and n2 can be independently 0 or 1. When n1 or n2 is 0, the corresponding L 2 Or L 3 It is to be understood that the groups are attached directly to each oxygen atom.
[0041] Non-limiting examples of repeat units having acid labile groups include: [ka] [ka] [ka] [ka] (In the formula, R dis hydrogen, halogen, substituted or unsubstituted C 1~6 Alkyl or substituted or unsubstituted C 3~6 cycloalkyl) Examples include:
[0042] The repeat units in a block of a block copolymer that contain acid labile groups may typically be present in an amount of 10 to 90 mole percent (mol %), more typically 10 to 65 mol %, and even more typically 15 to 60 mol %, based on the total repeat units of the block. The repeat units that contain acid labile groups may typically be present in the block copolymer in an amount of 10 to 90 mol %, more typically 10 to 65 mol %, and even more typically 25 to 60 mol %, based on the total repeat units of the block copolymer.
[0043] The repeating unit of the block copolymer may include a lactone group. For example, the repeating unit of the block copolymer may include a lactone group represented by formula (6). [ka]
[0044] In equation (6), R a is hydrogen, fluorine, cyano, or substituted or unsubstituted C 1~10 It may be alkyl. Preferably, R a is hydrogen, fluorine or substituted or unsubstituted C 1~5 It may be an alkyl, typically hydrogen or methyl.
[0045] In equation (6), L 4 can be a single bond or one or more divalent linking groups. For example, L 4 -O-, -C(O)-, -C(O)O-, -N(R c )-, -C(O)N(R c )-, substituted or unsubstituted C 1~10 Alkylene, substituted or unsubstituted C 3~10 Cycloalkylene, substituted or unsubstituted C 3~10 Heterocycloalkylene, substituted or unsubstituted C 6~10Arylene, substituted or unsubstituted C 3~10 R may be heteroarylene or a combination thereof; c is hydrogen, substituted or unsubstituted C 1~30 Alkyl, substituted or unsubstituted C 1~30 Heteroalkyl, substituted or unsubstituted C 3~30 Cycloalkyl, substituted or unsubstituted C 1~30 Heterocycloalkyl, substituted or unsubstituted C 2~30 Alkenyl, substituted or unsubstituted C 2~30 Alkynyl, substituted or unsubstituted C 6~30 Aryl, substituted or unsubstituted C 7~30 Aryl alkyl, substituted or unsubstituted C 7~30 Alkylaryl, substituted or unsubstituted C 2~30 Heteroaryl, substituted or unsubstituted C 3~30 Heteroarylalkyl or substituted or unsubstituted C 3~30 In some embodiments, L can be alkyl, heteroaryl, or both. 4 is a single bond or -C(O)O-, substituted or unsubstituted C 1~10 Alkylene, substituted or unsubstituted C 3~10 Cycloalkylene, substituted or unsubstituted C 3~10 Heterocycloalkylene, substituted or unsubstituted C 6~10 Arylene, substituted or unsubstituted C 3~10 heteroarylene, or a combination thereof.
[0046] In equation (6), R 7 is a monocyclic, polycyclic or fused polycyclic C 4~20 It may be a lactone-containing group.
[0047] Non-limiting examples of lactone-containing repeat units of formula (6) include: [ka] (In the formula, R d is hydrogen, fluorine, cyano, or substituted or unsubstituted C 1~10 (which may be alkyl) Preferably, R d is hydrogen, fluorine or substituted or unsubstituted C 1~5 It may be an alkyl, typically methyl.
[0048] The repeat units in a block of a block copolymer that contain a lactone group may typically be present in an amount of 20 to 90 mol %, more typically 25 to 75 mol %, and even more typically 30 to 70 mol %, based on the total repeat units of the block. The repeat units that contain a lactone group may typically be present in a block copolymer in an amount of 20 to 90 mol %, more typically 25 to 75 mol %, and even more typically 30 to 70 mol %, based on the total repeat units of the block copolymer.
[0049] The repeat unit of the block copolymer may include a salt group. As used herein, "salt group" refers to a moiety having a positive charge and a negative charge, such as having a positively or negatively charged moiety pendantly attached to the backbone of the block copolymer. The repeat unit of the block copolymer that includes a salt group may include a photoacid generator (PAG) group or a photodegradable quencher (PDQ) group. For example, the repeat unit of the block copolymer may include a salt group represented by formula (7a) or (7b). [ka]
[0050] In formulas (7a) and (7b), each R m is hydrogen, fluorine, cyano, or substituted or unsubstituted C 1~10 It may be alkyl. Preferably, R m is hydrogen, fluorine or substituted or unsubstituted C 1~5 It is an alkyl group, typically methyl.
[0051] In equations (7a) and (7b), Q 1 and Q 2 may each independently be a single bond or a divalent linking group. 1 and Q 2may each independently contain 1 to 10 carbon atoms and at least one heteroatom, more preferably -C(O)-O-.
[0052] In equations (7a) and (7b), A 1 and A 2 are each independently a substituted or unsubstituted C 1~30 Alkylene, substituted or unsubstituted C 3~30 Cycloalkylene, substituted or unsubstituted C 2~30 Heterocycloalkylene, substituted or unsubstituted C 6~30 Arylene or substituted or unsubstituted C 3~30 In some embodiments, A may be one or more of a heteroarylene. 1 and A 2 each independently represents an optionally substituted divalent C 1~30 It may be a perfluoroalkylene group.
[0053] In equation (7a), Z - A 1 The anionic moiety attached to the conjugate acid typically has a pKa of -15 to 10. - can be a sulfonate, carboxylate, anion of a sulfonamide, an anion of a sulfonimide, or a methide anion.
[0054] In equation (7a), G + is an organic cation as defined herein. In some embodiments, G + is an iodonium cation substituted with two alkyl groups, two aryl groups, or a combination of an alkyl group and an aryl group, or a sulfonium cation substituted with three alkyl groups, three aryl groups, or a combination of an alkyl group and an aryl group.
[0055] In equation (7b), Z - is an anionic compound as defined herein, the conjugate acid of which typically has a pKa of -15 to 10. -can be a sulfonate, carboxylate, anion of a sulfonamide, anion of a sulfonimide, or a methide anion species. For example, Z - is an anion A - may be as defined herein with respect to
[0056] In equation (7b), G + A 2 For example, G + may include an iodonium cation substituted with two alkyl groups, two aryl groups, or a combination of an alkyl and an aryl group, or a sulfonium cation substituted with three alkyl groups, three aryl groups, or a combination of an alkyl and an aryl group.
[0057] In yet other embodiments, when the block copolymer includes a repeat unit having a salt group, the block copolymer can include a zwitterionic species. For example, a block of the block copolymer can be represented by formula (7c): [ka] (In formula (7c), each R m are independently as defined for formulas (7a) and (7b). The repeat unit may include a repeat unit having a salt group.
[0058] In equation (7c), Q 1 , A 1 and Z - is defined as in equation (7a), and Q 2 , A 2 and G + is as defined in equation (7b).
[0059] Exemplary repeat units of formula (7a) include: [ka] [ka] (wherein G is an organic cation; each R d are independently as defined for formula (7a). Includes:
[0060] Exemplary repeat units of formula (7b) include: [ka] (In the formula, Z - is an anionic group as defined herein, and each R d are independently as defined for formula (7b). Includes:
[0061] The repeat units containing a salt group in a block of a block copolymer may typically be present in an amount of 1 to 35 mol %, typically 1 to 25 mol %, more typically 2 to 15 mol %, based on the total repeat units of the block. The repeat units containing a salt group may be present in the block copolymer in an amount of 1 to 35 mol %, typically 1 to 25 mol %, more typically 2 to 15 mol %, based on the total repeat units of the block copolymer.
[0062] The repeat unit of the block copolymer may include a hydroxyaryl group. Exemplary hydroxyaryl groups include phenol groups or naphthol groups. For example, the repeat unit of the block copolymer may include a hydroxyaryl group represented by formula (8): [ka]
[0063] In equation (8), R a is hydrogen, fluorine, cyano, or substituted or unsubstituted C 1~10 It may be alkyl. Preferably, R a is hydrogen, fluorine or substituted or unsubstituted C 1~5 It may be an alkyl, typically hydrogen or methyl.
[0064] In equation (8), L 5can be a single bond or one or more divalent linking groups. For example, L 5 -O-, -C(O)-, -C(O)O-, -N(R c )-, -C(O)N(R c )-, substituted or unsubstituted C 1~10 Alkylene, substituted or unsubstituted C 3~10 Cycloalkylene, substituted or unsubstituted C 3~10 Heterocycloalkylene, substituted or unsubstituted C 6~10 Arylene, substituted or unsubstituted C 3~10 R may be heteroarylene or a combination thereof; c is hydrogen, substituted or unsubstituted C 1~30 Alkyl, substituted or unsubstituted C 1~30 Heteroalkyl, substituted or unsubstituted C 3~30 Cycloalkyl, substituted or unsubstituted C 1~30 Heterocycloalkyl, substituted or unsubstituted C 2~30 Alkenyl, substituted or unsubstituted C 2~30 Alkynyl, substituted or unsubstituted C 6~30 Aryl, substituted or unsubstituted C 7~30 Aryl alkyl, substituted or unsubstituted C 7~30 Alkylaryl, substituted or unsubstituted C 2~30 Heteroaryl, substituted or unsubstituted C 3~30 Heteroarylalkyl or substituted or unsubstituted C 3~30 In some embodiments, L can be alkyl, heteroaryl, or both. 5 is a single bond or -C(O)O-, substituted or unsubstituted C 1~10 Alkylene, substituted or unsubstituted C 3~10 Cycloalkylene, substituted or unsubstituted C 3~10 Heterocycloalkylene, substituted or unsubstituted C 6~10 Arylene, substituted or unsubstituted C 3~10 heteroarylene, or a combination thereof.
[0065] In equation (8), Ar 1is a substituted C optionally containing one or more aromatic ring heteroatoms selected from N, O, S or combinations thereof; 5~60 It may be an aromatic group, and the aromatic group may be monocyclic, non-fused polycyclic or fused polycyclic. 5~60 When the aromatic group is polycyclic, the rings or ring groups can be fused (e.g., naphthyl, etc.), non-fused, or combinations thereof. 5~60 When the aromatic group is non-fused, the rings or ring groups can be directly linked (e.g., biaryl, biphenyl, etc.) or bridged by heteroatoms (e.g., triphenylamino or diphenylene ether, etc.). In some embodiments, polycyclic C 5~60 The aromatic groups can contain a combination of fused and directly linked rings (eg, binaphthyl, etc.).
[0066] In formula (8), y can be an integer from 1 to 12, preferably from 1 to 6, and typically from 1 to 3.
[0067] In equation (8), each R x At least one R x may independently be hydrogen or methyl, provided that is hydrogen.
[0068] Non-limiting examples of such repeat units of formula (8) include: [ka] (In the formula, R d is hydrogen, fluorine, cyano, or substituted or unsubstituted C 1~10 (which may be alkyl) Preferably, R d is hydrogen, fluorine or substituted or unsubstituted C 1~5 It may be an alkyl, typically methyl.
[0069] The repeat units in a block of a block copolymer that contain a hydroxyaryl group may typically be present in an amount of 10 to 90 mole percent (mol%), more typically 15 to 75 mol%, and even more typically 25 to 70 mol%, based on the total repeat units of the block. The repeat units that contain a hydroxyaryl group may typically be present in a block copolymer in an amount of 10 to 90 mol%, more typically 15 to 75 mol%, and even more typically 25 to 70 mol%, based on the total repeat units of the block copolymer.
[0070] In some embodiments, the blocks of the block copolymer may optionally further include one or more additional repeat units. The additional repeat units may be, for example, one or more additional units for the purpose of adjusting the properties of the block copolymer. Exemplary additional repeat units may include those derived from one or more of (meth)acrylate, vinyl aromatic, vinyl ether, vinyl ketone and / or vinyl ester monomers. The one or more additional repeat units, when present in the block of the block copolymer, may be used in an amount of 80 mol % or less, typically 3 to 50 mol %, based on the total repeat units of the block. The one or more additional repeat units, when present, may be used in the block copolymer in an amount of 80 mol % or less, typically 3 to 50 mol %, based on the total repeat units of the block copolymer.
[0071] In some embodiments, the block copolymer may include repeating units that include polar groups. Exemplary polar groups include sultone groups, sulfonamide groups, hydroxyalkyl groups, hydroxycycloalkyl groups, or combinations thereof. Although some groups, such as lactone groups or hydroxyaryl groups, may be considered polar groups, it is understood that these groups are distinct from polar groups as used herein.
[0072] The repeating unit of the block copolymer may contain a polar group represented by formula (9). [ka]
[0073] In equation (9), R a is hydrogen, fluorine, cyano, or substituted or unsubstituted C 1~10 It may be alkyl. Preferably, R a is hydrogen, fluorine or substituted or unsubstituted C 1~5 It may be an alkyl, typically hydrogen or methyl.
[0074] In equation (9), L 6 can be a single bond or one or more divalent linking groups. For example, L 6 -O-, -C(O)-, -C(O)O-, -N(R c )-, -C(O)N(R c )-, substituted or unsubstituted C 1~10 Alkylene, substituted or unsubstituted C 3~10 Cycloalkylene, substituted or unsubstituted C 3~10 Heterocycloalkylene, substituted or unsubstituted C 6~10 Arylene, substituted or unsubstituted C 3~10 R may be heteroarylene or a combination thereof; c is hydrogen, substituted or unsubstituted C 1~30 Alkyl, substituted or unsubstituted C 1~30 Heteroalkyl, substituted or unsubstituted C 3~30 Cycloalkyl, substituted or unsubstituted C 1~30 Heterocycloalkyl, substituted or unsubstituted C 2~30 Alkenyl, substituted or unsubstituted C 2~30 Alkynyl, substituted or unsubstituted C 6~30 Aryl, substituted or unsubstituted C 7~30 Aryl alkyl, substituted or unsubstituted C 7~30 Alkylaryl, substituted or unsubstituted C 2~30 Heteroaryl, substituted or unsubstituted C 3~30 Heteroarylalkyl or substituted or unsubstituted C 3~30 In some embodiments, L can be alkyl, heteroaryl, or both. 6 is a single bond or -C(O)O-, substituted or unsubstituted C 1~10Alkylene, substituted or unsubstituted C 3~10 Cycloalkylene, substituted or unsubstituted C 3~10 Heterocycloalkylene, substituted or unsubstituted C 6~10 Arylene, substituted or unsubstituted C 3~10 heteroarylene, or a combination thereof.
[0075] In equation (9), R 8 is a substituted or unsubstituted C 1~100 Or C 1~20 Alkyl, typically C 1~12 Alkyl, substituted or unsubstituted C 3~30 Or C 3~20 Cycloalkyl or substituted or unsubstituted poly(C 1~3 alkylene oxide). 1~100 Or C 1~20 Alkyl, substituted C 3~30 Or C 3~20 Cycloalkyl and Substituted Poly(C 1~3 The alkylene oxide) is substituted with one or more sulfonamide groups (eg, -NHSO2CF3), hydroxy groups (-OH), or fluoroalcohol groups (eg, -C(CF3)2OH).
[0076] Non-limiting examples of repeat units of formula (9) include: [ka] (In the formula, R g is hydrogen, fluorine, cyano, or substituted or unsubstituted C 1~10 (which may be alkyl) Preferably, R g is hydrogen, fluorine or substituted or unsubstituted C 1~5 It may be an alkyl group, typically methyl. 1 is F or C 1~4 It may be a perfluoroalkyl.
[0077] In some embodiments, the block copolymer may include a repeat unit that includes an acid group. Exemplary acid groups include carboxylic acid groups. The repeat unit of the block copolymer may include an acid group represented by formula (10). [ka]
[0078] In equation (10), R a is hydrogen, fluorine, cyano, or substituted or unsubstituted C 1~10 It may be alkyl. Preferably, R a is hydrogen, fluorine or substituted or unsubstituted C 1~5 It may be an alkyl, typically hydrogen or methyl.
[0079] In equation (10), L 7 is a single bond or a substituted or unsubstituted C 1~30 Alkylene, substituted or unsubstituted C 3~30 Cycloalkylene, substituted or unsubstituted C 1~30 Heterocycloalkylene, substituted or unsubstituted C 6~30 Arylene, substituted or unsubstituted divalent C 7~30 Aryl alkyl, substituted or unsubstituted C 1~30 Heteroarylene or substituted or unsubstituted divalent C 3~30 It can be one or more of heteroarylalkyl or -C(O)-O-.
[0080] In equation (10), R 9 can be -C(O)-OH.
[0081] Non-limiting examples of repeat units of formula (10) include: [ka] (In the formula, R d is hydrogen, fluorine, cyano, or substituted or unsubstituted C 1~10 (which may be alkyl) Preferably, R dis hydrogen, fluorine or substituted or unsubstituted C 1~5 It may be an alkyl, typically methyl.
[0082] The repeat units in the block of the block copolymer that contain acid groups may typically be present in an amount of 1 to 20 mol %, more typically 5 to 20 mol %, and even more typically 5 to 10 mol %, based on the total repeat units of the block. The repeat units that contain hydroxyaryl groups may typically be present in the block copolymer in an amount of 1 to 20 mol %, more typically 5 to 20 mol %, and even more typically 5 to 10 mol %, based on the total repeat units of the block copolymer.
[0083] Non-limiting exemplary first and second blocks of the block copolymers of the present invention include: [ka] (In the formula, w1, w2, x1, x2, y1, y2, z1, and z2 each represent the mole percent of the repeating unit based on 100 mole percent of all repeating units in the block of the block copolymer.) Includes:
[0084] In block copolymers, the average number of repeat units in each block can be 5 or more. Typically, the average number of polymerized units in each block can be 10 or more, or 20 or more, or 100 or more. For example, a triblock copolymer containing three blocks can have a total repeat unit of 15 or more, or 30 or more, or 75 or more, or 150 or more.
[0085] In a block copolymer, the average number of blocks in the block copolymer can be from 3 to 10. Typically, a block copolymer can have an average number of blocks that is from 3 to 5.
[0086] The block copolymers typically have a weight average molecular weight (M) of 2,500 to 50,000 grams per mole (g / mol), preferably 2,500 to 30,000 g / mol, more preferably 2,500 to 20,000 g / mol, and even more preferably 2,500 to 15,000 g / mol. w ) M w Against M n The dispersibility index (D) of the block copolymer, which is the ratio of M n (wherein m is the number average molecular weight.) Molecular weights are determined by gel permeation chromatography (GPC) using polystyrene standards.
[0087] Also provided is a block copolymer comprising a plurality of block copolymers described herein, each of the block copolymers of the plurality of block copolymers being different. That is, one embodiment provides a block copolymer derived from a plurality of block copolymers described herein, each of the block copolymers of the plurality of block copolymers being different. For example, such a block copolymer may include a first segment derived from a first block copolymer having a first gradient of repeat units and a second segment derived from a second block copolymer having a second gradient of repeat units, the first gradient of repeat units and the second gradient of repeat units being different.
[0088] Another embodiment provides a polymer comprising one or more block copolymers, wherein the block copolymer is attached to another portion of the polymer. In other words, in some embodiments, the block copolymers described herein can be attached (e.g., grafted) to another polymer using any suitable method.
[0089] Block copolymers can be prepared by any suitable method in the art.For example, one or more monomers corresponding to the polymerization units described herein can be combined or separately fed and polymerized in a reactor using a suitable solvent and initiator.For example, block copolymers can be obtained by polymerization of each monomer under any suitable conditions, such as by heating at an effective temperature, irradiating with an effective wavelength of actinic radiation, or a combination thereof.
[0090] Each monomer corresponding to a repeat unit described herein independently contains a polymerizable group having a carbon-carbon unsaturated vinyl group, typically a substituted or unsubstituted C 2~20 The polymerizable group of each monomer may be independently selected from a substituted or unsubstituted C2 to C3 alkyl group, a substituted or unsubstituted norbornyl group, a substituted or unsubstituted (meth)acrylic group, a substituted or unsubstituted vinyl ether group, a substituted or unsubstituted vinyl ketone group, a substituted or unsubstituted vinyl ester group, or a substituted or unsubstituted vinyl aromatic group. 20 alkenyl, substituted or unsubstituted norbornyl, substituted or unsubstituted (meth)acrylic or substituted or unsubstituted vinyl aromatic. Preferably, the polymerizable group of each monomer is independently substituted or unsubstituted (meth)acrylic or substituted or unsubstituted vinyl aromatic.
[0091] Block copolymers can be prepared using living or controlled free radical polymerization techniques, such as reversible addition-fragmentation chain transfer polymerization (RAFT), nitroxide-mediated polymerization (NMP), atom transfer radical polymerization (ATRP), and the like. Unlike controlled free radical polymerization, conventional free radical polymerization often proceeds at a relatively uncontrolled rate until the exhaustion of monomer reactants. Although average molecular weight can generally be controlled by controlling initiator loading, monomer loading, initiation rate, termination rate, and propagation rate, conventional free radical polymerization can result in a wide range of polymer chain lengths in a population of polymer molecules, resulting in highly polydisperse polymers, since chain termination reactions are difficult to precisely control when they could occur on any individual macroradical chain. Controlled free radical polymerization occurs when side reactions that lead to polymer chain termination are eliminated or significantly reduced, and the degree of polymerization is manipulated by controlling the equilibrium of the reversible conversion of living polymer chains between active form macroradicals that will propagate chain growth and inactive or dormant macromolecules that cannot propagate chain growth unless they are converted to active macroradical form. Controlled radical polymerization can thus produce block copolymers by free radical chain extension, the molecular weight of which is easily controlled and with improved lower polydispersity.
[0092] The polymerization may use chain transfer agents (CTAs) including thiocarbonylthio compounds such as dithioesters, thiocarbamates, xanthates, etc., to mediate the polymerization via a reversible chain transfer process. In some embodiments, block copolymers may be produced by reacting selected monomers with a dithioester chain transfer agent and an initiator to produce the block copolymer. In some embodiments, the initiator may be light.
[0093] Exemplary chain transfer agents (CTAs) for controlled free radical polymerization include thiocarbonylthio compounds such as 2-cyano-2-propylbenzodithioate, 4-cyano-4-(phenylcarbonothioylthio)pentanoic acid, 2-cyano-2-propyldodecyltrithiocarbonate, 4-cyano-4-[(dodecylsulfanylthiocarbonyl)sulfanyl]pentanoic acid, 2-(dodecylthiocarbonothioyl)-2-methylpropionic acid, cyanomethyldodecyltrithiocarbonate, cyanomethylmethyl(phenyl)carbamodithioate, bis(thiobenzoyl)disulfide, bis(dodecylsulfanyl-thiocarbonyl)disulfide, and the like.
[0094] Examples of initiators include azobis(isobutyronitrile) (AIBN), azobis(2-methylbutyronitrile), azobis(2,4-dimethylvaleronitrile), azobis(4-cyanovaleric acid). Examples of peroxide and peroxy initiators include hydrogen peroxide, sodium peroxide, potassium peroxide, t-butyl hydroperoxide, cumene hydroperoxide, dilauroyl peroxide, tert-butyl peroxy neodecanoate, dibenzoyl peroxide, cumyl peroxide, tert-butyl peroxy-2-ethylhexanoate, tert-butyl peroxy diethyl acetate, and tert-butyl peroxy benzoate. Examples of additional initiators include ammonium and / or alkali metal persulfates, sodium perborate, perphosphoric acid and its salts, potassium permanganate and ammonium or alkali metal salts of peroxodisulfate (e.g., alkali metal or ammonium peroxodisulfates), diacetyl peroxide, dibenzoyl peroxide, succinyl peroxide, di-tert-butyl peroxide, tert-butyl perbenzoate, tert-butyl perpivalate, tert-butyl peroxy-2-ethylhexanoate, permaleic acid ... Examples of suitable initiators include tert-butyl peroxyacetate, cumene hydroperoxide, diisopropyl peroxydicarbamate, bis(o-toluoyl)peroxide, didecanoyl peroxide, dioctanoyl peroxide, dilauroyl peroxide, tert-butyl perisobutyrate, tert-butyl peracetate, di-tert-amyl peroxide, tert-butyl hydroperoxide, azobisisobutyronitrile, 2,2'-azobis(2-amidino-propane)dihydrochloride or 2,2'-azobis(2-methylbutyronitrile). Mixtures of these initiators are also suitable. It is also possible to use reduction / oxidation (i.e. redox) initiator systems as initiators. Redox initiator systems consist of at least one reducing agent, usually inorganic, and one organic or inorganic oxidizing agent. The oxidizing component comprises, for example, a polymerization initiator as already specified above.The reducing component includes, for example, sodium sulfite, alkali metal salts of sulfite such as sodium hydrogen sulfite, alkali metal salts of disulfite such as sodium disulfite, bisulfite adducts of aliphatic aldehydes and ketones such as acetone bisulfite, or reducing agents such as hydroxymethane sulfite and its salts or ascorbic acid. The redox initiator system can be used together with a soluble metal compound whose metal component can exist in multiple valence states. Typical redox initiator systems are, for example, ascorbic acid / iron(II) sulfate / sodium peroxodisulfate, tert-butyl hydroperoxide / sodium disulfite, tert-butyl hydroperoxide / Na hydroxymethanesulfinate. Individual components, such as the reducing component, can also be mixtures, an example being a mixture of the sodium salt of hydroxymethanesulfinic acid and sodium disulfite.
[0095] Nitroxide-mediated polymerization, i.e., NMP, using stable nitroxide radicals or alkoxyamines as initiators, can also be used to prepare block copolymers. Examples of suitable initiators for NMP include N-tert-butyl-N-(2-methyl-1-phenylpropyl)-O-(1-phenylethyl)hydroxylamine, N-tert-butyl-O-[1-[4-(chloromethyl)phenyl]ethyl]-N-(2-methyl-1-phenylpropyl)hydroxylamine, 2,2,5-trimethyl-4-phenyl-3-azahexane-3-nitroxide, 2,2,6,6-tetramethyl-1-piperidinyloxy (TEMPO), etc.
[0096] Block copolymers can also be prepared using atom transfer radical polymerization, i.e., ATRP. Suitable initiators for ATRP include α-bromoisobutyrate tert-butyl, α-bromoisobutyryl bromide, 2-bromoisobutyrate dodecyl, α-bromoisobutyrate ethyl, α-bromoisobutyrate methyl, 2-bromoisobutyrate octadecyl, and the like. Suitable catalysts for ATRP include copper(I) chloride, copper(II) chloride, copper(I) bromide, copper(II) bromide, copper(I) iodide, and the like. Suitable ligands for ATRP include tris(2-pyridylmethyl)amine, tris[2-(dimethylamino)ethyl]amine, 4,4'-dinonyl-2,2'-dipyridyl, N,N,N',N",N"-pentamethyldiethylenetriamine, and the like.
[0097] The initiator may be used in a molar ratio to the chain transfer agent of from 0.05 to 2. In an exemplary embodiment, the initiator may be used in a molar ratio to the chain transfer agent of from 0.07 to 1.
[0098] The amount of initiator is generally at least 0.01 or 0.05 or 0.01% to 10 or 5 or 3% by weight based on all of the monomers being polymerized.
[0099] The polymerization reaction used to prepare the block copolymers can be carried out in any suitable solvent, although the polymerization can also proceed in the absence of a solvent. Exemplary polymerization solvents include ethers, cyclic ethers, C5- 10 Included are alkanes, C5-8 cycloalkanes which may be substituted with one to three C1-4 alkyl groups, aromatic hydrocarbon solvents, halogenated hydrocarbon solvents, acetonitrile, dimethylformamide, ethylene carbonate, propylene carbonate, dimethylsulfoxide, dimethylsulfone, water, mixtures of such solvents, supercritical solvents (such as CO2, C1-4 alkanes in which any H may be replaced with F, etc.), or combinations thereof.
[0100] A typical procedure for preparing a block copolymer is as follows: A mixture of monomers is typically prepared in a solvent and combined with an initiator. This solution can be degassed with nitrogen and placed in a syringe as a feed mixture. A portion of the feed mixture can then be added to a heated reaction vessel containing a chain transfer agent, and polymerization can proceed for a period of time to form a first block of the block copolymer. A second portion of the feed mixture can then be added to the heated reaction vessel, and polymerization can proceed for a period of time to form a second block of the block copolymer. Additional blocks of the copolymer can be formed using a similar sequence of steps. While the above example provides a single feed mixture in which the ratio of monomers remains constant for each subsequently formed block of the block copolymer, in other embodiments, different feed mixtures can be added at each step to vary the ratio of monomers used to prepare each block of the block copolymer. For block copolymers that include additional blocks other than the first and second blocks described herein, different feed mixtures may be used to form the third and subsequent blocks such that each block may have the same or different compositions and / or ratios.
[0101] After the polymerization is completed, the formed block copolymer is isolated. The isolation step can be carried out by known procedures and can include evaporating any remaining monomers and / or solvent, precipitating in a suitable solvent, filtering or centrifuging the precipitated block copolymer, washing the block copolymer, and drying the washed block copolymer. The transition metal compound can be removed by passing through a column or pad of alumina, silica and / or clay. Alternatively, the transition metal compound can be oxidized (if necessary) and retained in the block copolymer as a stabilizer. The chain terminating group, if present, can be cleaved from the block copolymer using any suitable method known in the art.
[0102] Precipitation may typically be carried out using a suitable C5-8 alkane or C5-8 cycloalkane solvent such as pentane, hexane, heptane, cyclohexane or mineral spirits, or using a C1-6 alcohol such as methanol, ethanol or isopropanol, or a combination of suitable solvents.
[0103] Also provided is a photoresist composition comprising a block copolymer as described herein and a solvent. In some embodiments, the photoresist composition can comprise a block copolymer as described herein, a photoacid generator, and a solvent. In yet other embodiments, the photoresist composition can comprise a first polymer that is a block copolymer as described herein, a photoacid generator, and a solvent, and can further comprise a second (different) polymer that is structurally different from the first polymer (block copolymer).
[0104] The second polymer may include one or more polymerized (e.g., repeating) units, such as those described herein. Exemplary second polymers may be polyacrylates, polyvinyl ethers, polyesters, polynorbornenes, polyacetals, polyethylene glycols, polyamides, polyacrylamides, polyphenols, novolacs, styrene polymers, polyvinyl alcohols, or combinations thereof. For example, the second polymer may include repeating units that include acid labile groups, hydroxyaryl groups, fluoroalcohol groups, sulfonamide groups, lactone groups, or combinations thereof.
[0105] The second polymer typically has an M of 1,000 to 50,000 g / mol, in particular 2,000 to 30,000 g / mol, more in particular 3,000 to 20,000 g / mol, and even more in particular 3,000 to 10,000 g / mol. w M w Against M n The PDI of the polymer, which is the ratio of the PDI to the PDI, is typically 1.1 to 3, especially 1.1 to 2. Molecular weights are determined by GPC using polystyrene standards.
[0106] The second polymer can be prepared by any suitable method in the art.For example, one or more monomers corresponding to the polymerized units described herein can be combined or separately fed and polymerized in a reactor using a suitable solvent and initiator.For example, the second polymer can be obtained by polymerization of each monomer under any suitable conditions, such as by heating at an effective temperature, irradiating with actinic radiation at an effective wavelength, or a combination thereof.
[0107] The photoresist composition includes a solvent for dissolving the components of the composition and facilitating its coating on a substrate. Preferably, the solvent is an organic solvent conventionally used in the manufacture of electronic devices. Suitable solvents include, for example, aliphatic hydrocarbons such as hexane and heptane; aromatic hydrocarbons such as toluene and xylene; halogenated hydrocarbons such as dichloromethane, 1,2-dichloroethane and 1-chlorohexane; alcohols such as methanol, ethanol, 1-propanol, isopropanol, tert-butanol, 2-methyl-2-butanol and 4-methyl-2-pentanol; ethers such as propylene glycol monomethyl ether (PGME), diethyl ether, tetrahydrofuran, 1,4-dioxane and anisole; ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, 2-heptanone and cyclohexanone (CHO). esters such as ethyl acetate, n-butyl acetate, propylene glycol monomethyl ether acetate (PGMEA), ethyl lactate (EL), hydroxyisobutyric acid methyl ester (HBM) and ethyl acetoacetate; lactones such as gamma-butyrolactone (GBL) and epsilon-caprolactone; lactams such as N-methylpyrrolidone; nitriles such as acetonitrile and propionitrile; cyclic or acyclic carbonate esters such as propylene carbonate, dimethyl carbonate, ethylene carbonate and diphenyl carbonate; polar aprotic solvents such as dimethylsulfoxide and dimethylformamide, water and combinations thereof. Of these, preferred solvents are PGME, PGMEA, EL, GBL, HBM, CHO and combinations thereof. The total solvent content (i.e., the cumulative solvent content of all solvents) in a photoresist composition is typically 40 to 99 weight percent (wt %), more typically 70 to 99 wt %, and even more typically 85 to 99 wt %, based on the total weight of the photoresist composition. The desired solvent content will depend, for example, on the desired thickness of the coated photoresist layer and the coating conditions.
[0108] In the photoresist composition, the block copolymer will typically be present in the photoresist composition in an amount of from 10 to 99.9 weight percent, typically from 25 to 99 weight percent, more typically from 50 to 95 weight percent, based on the total solids content of the photoresist composition, it being understood that the total solids content includes the block copolymer, the PAG and other non-solvent components.
[0109] The photoresist composition may further comprise a photoacid generator (PAG). The PAG may be ionic or non-ionic. The PAG may be in polymeric or non-polymeric form. In the polymeric form, the PAG may be present as a moiety in a repeat unit of the polymer derived from a polymerizable PAG monomer. In some embodiments, the block copolymer may further comprise a repeat unit that includes PAG functionality (e.g., as a salt group of the repeat unit).
[0110] Suitable PAG compounds are of formula G + A - (In the formula, G + is a photoactive cation, and A - is an anion capable of generating a photoacid. The PAG cation is preferably selected from an onium cation, preferably an iodonium cation or a sulfonium cation. Particularly suitable anions include those whose conjugate acids have a pKa of -15 to 10. The PAG anion is typically an organic anion having a sulfonate group or a non-sulfonate type group such as a sulfonamidate, sulfonimidate, methide or borate.
[0111] In some embodiments, the PAG cation can be a sulfonium cation or an iodonium cation, for example, the PAG cation can be a sulfonium cation of formula (10) or an iodonium cation of formula (11). [ka]
[0112] In equations (10) and (11), R17 ~R 21 are each independently a substituted or unsubstituted C 1~20 Alkyl, substituted or unsubstituted C 3~20 Cycloalkyl, substituted or unsubstituted C 2~20 Alkenyl, substituted or unsubstituted C 6~30 Aryl, substituted or unsubstituted C 6~30 Iodoaryl, substituted or unsubstituted C 3~30 Heteroaryl, substituted or unsubstituted C 7~20 Arylalkyl or substituted or unsubstituted C 4~20 R can be heteroaryl, alkyl, or a combination thereof. 17 ~R 19 may be separate or may be connected to R via a single bond or a divalent linking group. 17 ~R 19 R may be linked to another group to form a ring. 20 and R 21 R can be either separate or can be linked together via a single bond or a divalent linking group to form a ring. 17 ~R 21 Each of R may optionally include a divalent linking group as part of its structure. 17 ~R 21 Each of may optionally include acid labile groups independently selected from, for example, a tertiary alkyl ester group, a secondary or tertiary aryl ester group, a secondary or tertiary ester group having a combination of alkyl and aryl groups, a tertiary alkoxy group, an acetal group, or a ketal group.
[0113] Exemplary sulfonium cations of formula (10) can include one or more of the following: [ka] [ka]
[0114] Exemplary iodonium cations of formula (11) can include one or more of the following: [ka]
[0115] Exemplary organic anions having a sulfonate group can include one or more of the following: [ka]
[0116] Exemplary non-sulfonated anions can include one or more of the following: [ka]
[0117] Commonly used onium salts can include, for example, triphenylsulfonium trifluoromethanesulfonate, (p-tert-butoxyphenyl)diphenylsulfonium trifluoromethanesulfonate, tris(p-tert-butoxyphenyl)sulfonium trifluoromethanesulfonate, triphenylsulfonium p-toluenesulfonate, di-t-butylphenyliodonium perfluorobutanesulfonate, and di-t-butylphenyliodonium camphorsulfonate. Other useful PAG compounds are known in the chemically amplified photoresist art, such as nonionic sulfonyl compounds, such as 2-nitrobenzyl-p-toluenesulfonate, 2,6-dinitrobenzyl-p-toluenesulfonate, and 2,4-dinitrobenzyl-p-toluenesulfonate; sulfonic acid esters, such as 1,2,3-tris(methanesulfonyloxy)benzene, 1,2,3-tris(trifluoromethanesulfonyloxy)benzene, and 1,2,3-tris(p-toluenesulfonyloxy)benzene; diazomethane derivatives, such as bis(benzenesulfonyl)diazomethane, bis(p-toluenesulfonyl)diamine ... They may include azomethane; glyoxime derivatives such as bis-O-(p-toluenesulfonyl)-α-dimethylglyoxime and bis-O-(n-butanesulfonyl)-α-dimethylglyoxime; sulfonate derivatives of N-hydroxyimide compounds such as N-hydroxysuccinimide methanesulfonate, N-hydroxysuccinimide trifluoromethanesulfonate; and halogen-containing triazine compounds such as 2-(4-methoxyphenyl)-4,6-bis(trichloromethyl)-1,3,5-triazine and 2-(4-methoxynaphthyl)-4,6-bis(trichloromethyl)-1,3,5-triazine. Suitable photoacid generators are further described in (Patent Document 3) and (Patent Document 4).
[0118] Typically, when the photoresist composition includes a non-polymeric PAG, the PAG is present in the photoresist composition in an amount of from 0.1 to 55 weight percent, more typically from 1 to 25 weight percent, based on the total solids content of the photoresist composition. If present in polymeric form, the PAG is typically included in the polymer in an amount of from 1 to 25 mol %, more typically from 1 to 20 mol % or 2 to 10 mol %, based on the total polymerized units in the polymer.
[0119] In some embodiments, the anion and / or cation of the PAG does not contain and is free of -F, -CF3 or -CF2- groups. "Does not contain -F, -CF3 or -CF2- groups" is understood to mean that the anion and / or cation of the PAG excludes groups such as -CH2CF3 and -CH2CF2CH3. In yet other embodiments, the anion and / or cation of the PAG does not contain fluorine (i.e., does not contain fluorine atoms and is not substituted with fluorine-containing groups). In some embodiments, the photoacid generator does not contain fluorine (i.e., both the photoactive cation and the anion do not contain fluorine).
[0120] In some aspects, the photoresist composition may further comprise a surfactant. Preferably, the surfactant is hydrophobic and substantially immiscible with and has a lower surface energy than the block copolymer and other solid components of the photoresist composition. When coated on a substrate, the surfactant may thereby separate from the other solid components of the photoresist composition to the top surface of the formed photoresist layer. The surfactant may provide beneficial surface properties to the photoresist composition when coated on a substrate. For example, in an immersion exposure process, the surfactant may act as a barrier layer between the immersion fluid, typically water, contained between the lenses of the exposure tool, and the photoresist layer. This may minimize or prevent leaching of components of the underlying portion of the photoresist into the immersion fluid, which may otherwise cause contamination of the lenses and alter the effective refractive index and transmission properties of the immersion fluid. Due to its hydrophobicity, the surfactant may enable a high receding contact angle with respect to the immersion fluid, which may enable faster scanning speeds and increased process output. In immersion and non-immersion exposure processes, surface-active materials can also have a beneficial effect on reducing patterning defects such as bridging defects in closed contacts and in-line space patterns.
[0121] The surface active material is preferably soluble in the developer or becomes soluble in the developer during pattern formation, such as by interaction with the generated photoacid or with the developer. In some embodiments, the surface active material can be a polymeric material. The surface active material can be a homopolymer or a copolymer containing two, three or more different types of repeat units. In some embodiments, the surface active material can be a non-polymer in the form of a single molecule. Suitable surface active materials include, for example, one or more groups selected from acid groups such as carboxylic or sulfonic acid groups, acid labile groups, base labile groups, base soluble groups such as fluoroalcohol or phenol groups, alkyl groups, fluoroalkyl groups, ester groups, and combinations thereof. In the case of an aqueous base developer, such as a 0.26 normal (N) aqueous solution of tetramethylammonium hydroxide (TMAH), the surface active polymer preferably includes one or more base labile or base soluble groups to enhance solubility in the developer after exposure to activating radiation and post-exposure baking.
[0122] If present, surface active materials are typically present in photoresist compositions in an amount of from 0.01 to 10% by weight, typically from 1 to 5% by weight, based on total solids of the photoresist composition.
[0123] The photoresist composition may further comprise one or more additional, optional additives. For example, optional additives may include actinic dyes and contrast agents, anti-striation agents, plasticizers, rate enhancers, sensitizers, photolytic quenchers (PDQs) (also known as photolytic bases), base quenchers, thermal acid generators, surfactants, and the like, or combinations thereof. When present, optional additives are typically present in the photoresist composition in an amount of 0.01 to 10 weight percent based on the total solids content of the photoresist composition.
[0124] PDQ generates a weak acid upon irradiation. The acid generated from the photolytic deactivator is not strong enough to react quickly with the acid labile groups present in the resist matrix. Exemplary photolytic deactivators include, for example, photolytic cations, preferably C1~20 Carboxylic acid or C 1~20 Also included are those useful for preparing strong acid generator compounds paired with anions of weak acids (pKa>1), such as anions of sulfonic acids. Exemplary carboxylic acids include formic acid, acetic acid, propionic acid, tartaric acid, succinic acid, cyclohexane carboxylic acid, benzoic acid, salicylic acid, and the like. Exemplary sulfonic acids include p-toluenesulfonic acid, camphorsulfonic acid, and the like. In a preferred embodiment, the photolytic quencher is a photolytic organic zwitterionic compound, such as diphenyliodonium-2-carboxylate.
[0125] The PDQ may be in a non-polymeric form or in a polymer-bound form. Polymerized units containing a photodegradable quencher are typically present in an amount of 0.1 to 30 mol %, preferably 1 to 10 mol %, more preferably 1 to 2 mol %, based on the total repeat units of the polymer.
[0126] Exemplary basic quenching agents include, for example, linear aliphatic amines such as tributylamine, trioctylamine, triisopropanolamine, tetrakis(2-hydroxypropyl)ethylenediamine; n-tert-butyldiethanolamine, tris(2-acetoxy-ethyl)amine, 2,2',2'',2'''-(ethane-1,2-diylbis(azanetriyl))tetraethanol, 2-(dibutylamino)ethanol, and 2,2',2''-nitrilotriethanol; cyclic aliphatic amines such as N-(2-acetoxy-ethyl)morpholine, tert-butyl 1-pyrrolidinecarboxylate, tert-butyl 2-ethyl-1H-imidazole-1-carboxylate, di-tert-butylpiperazine-1,4-dicarboxylate, and N-(2-acetoxy-ethyl)morpholine; aromatic amines such as pyridine, di-tert-butylpyridine, and pyridinium; N,N-bis(2-hydroxyethyl)pivalamide, N,N-diethylacetamide, N 1 ,N 1 ,N 3 ,N 3linear and cyclic amides and derivatives thereof, such as tetrabutylmalonamide, 1-methylazepan-2-one, 1-allylazepan-2-one and tert-butyl 1,3-dihydroxy-2-(hydroxymethyl)propan-2-ylcarbamate; ammonium salts, such as quaternary ammonium salts of sulfonates, sulfamates, carboxylates and phosphonates; imines, such as primary and secondary aldimines and ketimines; optionally substituted diazines, such as pyrazines, piperazines and phenazines; optionally substituted diazoles, such as pyrazoles, thiadiazoles and imidazoles; and optionally substituted pyrrolidones, such as 2-pyrrolidone and cyclohexylpyrrolidone.
[0127] The basic quenching agent may be in a non-polymeric form or in a polymer-bound form. When in a polymeric form, the quenching agent may be present in a repeat unit of the polymer. The repeat unit containing the quenching agent is typically present in an amount of 0.1 to 30 mol %, preferably 1 to 10 mol %, more preferably 1 to 2 mol %, based on the total repeat units of the polymer.
[0128] Exemplary surfactants include fluorinated and non-fluorinated surfactants, and can be ionic or non-ionic, with non-ionic surfactants being preferred.Exemplary fluorinated non-ionic surfactants include perfluorinated C4 surfactants such as FC-4430 and FC-4432 surfactants (3M Corporation) and fluorodiols such as POLYFOX™ PF-636, PF-6320, PF-656 and PF-6520 fluorosurfactants (Omnova).In one embodiment, the photoresist composition further comprises a surfactant polymer that comprises a fluorine-containing repeat unit.
[0129] A method of forming a pattern is also provided. According to one embodiment, the method of forming a pattern includes applying a layer of a photoresist composition onto a substrate to form a photoresist composition layer, patternwise exposing the photoresist composition layer to activating radiation to form an exposed photoresist composition layer, and developing the exposed photoresist composition layer to provide a resist relief image. The photoresist composition includes a block copolymer as described herein and a solvent.
[0130] Here, a method of forming a pattern using the photoresist composition of the present invention is described. Suitable substrates onto which the photoresist composition can be coated include electronic device substrates. A variety of electronic device substrates, such as semiconductor wafers, polycrystalline silicon substrates, packaging substrates such as multichip modules, flat panel display substrates, substrates for light emitting diodes (LEDs) such as organic light emitting diodes (OLEDs), and the like, can be used in the present invention, with semiconductor wafers being typical. Such substrates are typically composed of one or more of silicon, polysilicon, silicon oxide, silicon nitride, silicon oxynitride, silicon germanium, gallium arsenide, aluminum, sapphire, tungsten, titanium, titanium-tungsten, nickel, copper, and gold. Suitable substrates can be in the form of wafers, such as those used in the manufacture of integrated circuits, optical sensors, flat panel displays, optical integrated circuits, and LEDs. Such substrates can be of any suitable size. A typical wafer substrate diameter is 200-300 millimeters (mm), although wafers having smaller and larger diameters can be suitably used in accordance with the present invention. The substrate may include one or more layers or structures that may optionally include active or operable portions of the device to be formed.
[0131] Typically, one or more lithographic layers, such as a hardmask layer, e.g., a spin-on carbon (SOC), amorphous carbon or metal hardmask layer, a CVD layer, such as a silicon nitride (SiN), silicon oxide (SiO) or silicon oxynitride (SiON) layer, an organic or inorganic underlayer, or a combination thereof, are provided on the upper surface of the substrate prior to coating the photoresist composition of the invention. Such layers, together with an overcoated photoresist layer, form a lithographic material stack.
[0132] Optionally, a layer of adhesion promoter can be applied to the substrate surface before coating the photoresist composition. If an adhesion promoter is desired, any suitable adhesion promoter for polymer films can be used, such as silanes, typically organosilanes such as trimethoxyvinylsilane, triethoxyvinylsilane, hexamethyldisilazane, or aminosilane couplers such as gamma-aminopropyltriethoxysilane. Particularly suitable adhesion promoters include those sold under the names AP™ 3000, AP™ 8000, and AP™ 9000S, available from DuPont Electronics & Industrial (Marlborough, Massachusetts).
[0133] The photoresist composition may be coated on the substrate by any suitable method, such as spin coating, spray coating, dip coating, doctor blading, and the like. For example, application of a layer of photoresist may be accomplished by spin coating the photoresist in a solvent using a coating track, where the photoresist is dispensed onto a rotating wafer. During dispensing, the wafer is typically spun at a speed of 4,000 revolutions per minute (rpm) or less, such as 200 to 3,000 rpm, for example 1,000 to 2,500 rpm, for 15 to 120 seconds to obtain a layer of photoresist composition on the substrate. It will be appreciated by those skilled in the art that the thickness of the coated layer may be adjusted by varying the spin speed and / or the total solids content of the composition. The photoresist composition layer formed from the composition of the present invention typically has a dry layer thickness of 3 to 30 micrometers (μm), preferably greater than 5 to 30 μm, more preferably 6 to 25 μm.
[0134] The photoresist composition is typically then soft baked to minimize the solvent content in the layer, thereby forming a tack-free coating and improving the adhesion of the layer to the substrate. The soft bake is performed, for example, on a hot plate or in an oven, with a hot plate being typical. The soft bake temperature and time will depend, for example, on the photoresist composition and thickness. The soft bake temperature is typically 80 to 170°C, more typically 90 to 150°C. The soft bake time is typically 10 seconds to 20 minutes, more typically 1 to 10 minutes, and even more typically 1 to 2 minutes. The heating time can be readily determined by one of ordinary skill in the art based on the components of the composition.
[0135] The photoresist layer is then patternwise exposed to activating radiation to effect solubility differences between exposed and unexposed regions. Reference herein to exposing the composition to radiation that activates the photoresist composition indicates that the radiation can form a latent image in the photoresist composition. Exposure is typically performed through a patterned photomask having optically transparent and optically opaque regions corresponding to the regions of the resist layer that are exposed and unexposed, respectively. Such exposure can alternatively be performed without a photomask in a direct write process typically used for e-beam lithography. Activating radiation typically has a wavelength of less than 400 nanometers (nm), less than 300 nm, or less than 200 nm, with wavelengths of 248 nm (KrF), 193 nm (ArF), 13.5 nm (EUV) or e-beam lithography being preferred. Preferably, the activating radiation is 193 nm radiation or EUV radiation. This method is utilized in immersion or dry (non-immersion) lithography techniques. Exposure energies are typically between 1 and 200 millijoules per square centimeter (mJ / cm), depending on the exposure tool and the components of the photoresist composition. 2 ), preferably 10 to 100 mJ / cm 2 , more preferably 20 to 50 mJ / cm 2 It is.
[0136] After exposure of the photoresist layer, a post-exposure bake (PEB) of the exposed photoresist layer is performed. PEB can be performed, for example, on a hotplate or in an oven, with a hotplate being typical. The conditions for PEB will depend, for example, on the photoresist composition and layer thickness. PEB is typically performed at a temperature of 70-150° C., preferably 75-120° C., for a time of 30-120 seconds. A latent image is formed in the photoresist, defined by polarity switching regions (exposed regions) and non-switching regions (unexposed regions).
[0137] The exposed photoresist layer is then developed with a suitable developer to selectively remove areas of the layer that are soluble in the developer, while the remaining insoluble areas form a resultant photoresist pattern relief image. In the case of a positive tone development (PTD) process, the exposed areas of the photoresist layer are removed during development, while the unexposed areas remain. Conversely, in a negative tone development (NTD) process, the exposed areas of the photoresist layer remain, while the unexposed areas are removed during development. Application of the developer can be accomplished by any suitable method, such as those described above with respect to application of the photoresist composition, with spin coating being typical. The development time is a period of time effective to remove the soluble areas of the photoresist, with times of 5 to 60 seconds being typical. Development is typically performed at room temperature.
[0138] Suitable developers for the PTD process include aqueous base developers, such as quaternary ammonium hydroxide solutions, such as TMAH, preferably 0.26N TMAH, tetraethylammonium hydroxide, tetrabutylammonium hydroxide, sodium hydroxide, potassium hydroxide, sodium carbonate, potassium carbonate, etc. Suitable developers for the NTD process are organic solvent based, meaning that the cumulative content of organic solvent in the developer is 50% by weight or more, typically 95% by weight or more, 98% by weight or more, or 100% by weight, based on the total weight of the developer. Suitable organic solvents for NTD developers include, for example, those selected from ketones, esters, ethers, hydrocarbons, and mixtures thereof. The developer is typically 2-heptanone or n-butyl acetate.
[0139] A coated substrate can be formed from the photoresist composition of the invention. Such a coated substrate comprises (a) a substrate having one or more layers to be patterned on its surface, and (b) a layer of a photoresist composition over the one or more layers to be patterned.
[0140] The photoresist pattern can be used, for example, as an etch mask, thereby allowing the pattern to be transferred to one or more successive underlying layers by known etching techniques, typically dry etching such as reactive ion etching. The photoresist pattern can be used, for example, for pattern transfer to an underlying hard mask layer, which in turn is used as an etch mask for pattern transfer to one or more layers below the hard mask layer. If the photoresist pattern is not consumed during pattern transfer, it can be removed from the substrate by known techniques, for example oxygen plasma ashing. The photoresist composition, when used in one or more such patterning processes, can be used to manufacture semiconductor devices such as memory devices, processor chips (CPUs), graphics chips, optoelectronic chips, LEDs, OLEDs, and other electronic devices.
[0141] The present invention is further illustrated by the following non-limiting examples. EXAMPLES
[0142] Synthesis Examples The synthesis reactions were carried out under a nitrogen atmosphere. Dimethyl 2,2'-azobis(2-methylpropionate) (V601) and 1,1'-azobis(cyclohexane-1-carbonitrile) (V40) initiators were purchased from Wako Specialty Chemicals. Diphenyliodonium-2-carboxylate monohydrate (DPIC), diphenyl(p-phenyl)sulfonium 2-(((3r,5r,7r)-adamantane-1-carbonyl)oxy)-1,1-difluoroethane-1-sulfonate (TDPS IAD), 4-(4-(tert-butyl)phenyl)-1,4-oxathia-4-nium tris((trifluoromethyl)sulfonyl)methanide (TBPTO C1), ethyl cyclopentyl methacrylate (ECPMA), γ-butyrolactone-2-yl methacrylate (α-GBLMA), 2-oxotetrahydro-2H-3,5-methanocyclopenta[b]furan-6-yl methacrylate (NLMA), propylene glycol monomethyl ether acetate (PGMEA), anisole, ethoxymethyl methacrylate (EOMMA), 5-methyl-3-methylenedihydrofuran-2(3H)-one (aMMBL), 2-(adamantan-1-yl)propan-2-yl methacrylate (IAM), 3-hydroxyadamantan-1-yl methacrylate (HAMA), (cyclohexyloxy)methyl methacrylate (CHOMMA), and 2-cyano-2-propyldodecyl trithiocarbonate were purchased from commercial sources and used without further purification.
[0143] ECPMA / α-GBLMA / NLMA copolymer synthesis [ka] Triblock copolymer synthesis. (ECPMA / α-GBLMA / NLMA) Triblock copolymers 1-4 were prepared as follows: A mixture of 26.1 grams (g) of ECPMA, 23.0 g of α-GBLMA, and 15.3 g of NLMA was mixed with 40.0 g of anisole to obtain a monomer solution with a solid content of 62% by weight. In a separate vial, 22.3 g of the as-prepared monomer solution was charged with 92 milligrams (mg) of V40 initiator. The solution was degassed with nitrogen and placed in a syringe as a feed mixture. 318 mg of 2-cyano-2-propyldodecyltrithiocarbonate was used as a chain transfer agent (CTA) in the reactor, protected under N2 at 110°C. 1 / 3 of the feed mixture was added to the reactor, and the resulting reaction mixture was heated for 120 minutes. Then, another 1 / 3 of the feed mixture was added to the reactor, and the reaction mixture was heated for another 120 minutes. The final 1 / 3 of the feed mixture was then added to the reactor and the reaction mixture was heated for 120 minutes. Aliquots were taken from the reaction mixture under gentle N2 flow for analysis as needed. The triblock copolymer was isolated by precipitation into isopropanol. Conversion reached over 90% at the end of the polymerization of each block.
[0144] Multiblock copolymer synthesis. (ECPMA / α-GBLMA / NLMA) Multiblock copolymer 5 was prepared as follows: A mixture of 8.83 g ECPMA, 7.51 g α-GBLMA, and 5.01 g NLMA was mixed with 14.21 g anisole to obtain a monomer solution with a solid content of 60 wt%. In a separate vial, 12.99 g of the as-prepared monomer solution was charged with 162 mg V40 initiator. The solution was degassed with nitrogen and placed in a syringe as a feed mixture. 225 mg 2-cyano-2-propyldodecyltrithiocarbonate was used as CTA in the reactor, protected under N2 at 110°C. 1 / 7 of the feed mixture was added to the reactor every hour and aliquots were taken from the reaction mixture under gentle N2 flow as needed. The polymer was isolated by precipitation into isopropanol. Conversion reached more than 90% at the end of the polymerization of each block.
[0145] End group removal The end groups were removed from copolymers 2, 4 and 5 by using the following procedure. Each block copolymer was dissolved in PGMEA with gentle heating (to obtain 15 wt % solids). After cooling to below 40° C., 20 equivalents of V601 initiator (relative to the trithiocarbonate groups of the block copolymer) were added to the solution. The solution was heated to 80° C. for 3 hours and precipitated in isopropanol to obtain block copolymers without trithiocarbonate end groups.
[0146] Comparative copolymers. (ECPMA / α-GBLMA / NLMA) Random copolymer 6 (comparative) was prepared as follows: A reactor was charged with 112 g of a degassed mixture of ethyl lactate (70 wt%) and 1,4-lactone (30 wt%) and heated to 80° C. A degassed monomer feed solution was prepared from a combination of 318.3 g of solvent (ethyl lactate / 1,4-lactone, 7:3 w / w), 95.9 g of ECPMA, 88.9 g of α-GBLMA, and 58 g of NLMA. Separately, a degassed initiator feed solution was prepared using 12.4 g of V601 initiator and 125.2 g of solvent (ethyl lactate / 1,4-lactone, 7:3 w / w). The monomer feed solution and the initiator feed solution were then added simultaneously to the reactor continuously, the monomer feed solution was added over 240 minutes, and the initiator feed solution was added over 210 minutes. The reactor was then cooled to ambient temperature at a rate of 1° C. / min. The copolymer was isolated by precipitation into methanol and the product was dried before use.
[0147] Random copolymer 7 (comparative) was prepared as follows: A reactor was charged with 11.2 g of degassed PGMEA and heated to 80° C. A degassed monomer feed solution was prepared from a combination of 10.245 g of ECPMA, 9.556 g of α-GBLMA, and 6.244 g of NLMA. Separately, a degassed initiator feed solution was prepared using 1.541 g of V601 and 13.902 g of PGMEA. The monomer feed solution and the initiator feed solution were then added simultaneously to the reactor continuously, the monomer feed solution was added over 240 minutes, and the initiator feed solution was added over 210 minutes. Five hours after the start of the feed solutions, the reactor was then cooled to ambient temperature at a rate of 1° C. / min. The copolymer was isolated by precipitation into methanol, and the product was dried before use.
[0148] The block copolymers derived from the monomer combination ECPMA / α-GBLMA / NLMA (40 / 40 / 20 molar ratio) and the comparative copolymers are summarized in Table 1.
[0149] [Table 1]
[0150] Synthesis of Additive E1 A monomer solution was prepared by combining 192.00 g of GMEA, 133.2 g of (methacryloyloxy)methylene bis(2,2-difluoro-3,3-dimethylbutanoate), and 8.51 g of ethylcyclopentyl methacrylate in a flask and stirring the resulting mixture to dissolve the components. Separately, an initiator solution was prepared by combining 10.72 g of PGMEA and 6.2 g of V601 initiator in a flask. 20.05 g of PGMEA was introduced into a separate reaction vessel and the vessel was purged with nitrogen for 30 minutes. The reaction vessel was then heated to 95° C. with stirring. The monomer solution and initiator solution were then introduced into the reaction vessel as separate feeds over a period of 2.5 hours. Upon completion of the 2.5 hours, the reaction vessel was maintained at 95° C. with stirring for an additional 3 hours and then allowed to cool to room temperature. Additive E1 has an M of 9.658 / 6.192 as measured by GPC using polystyrene standards. w / M n (kg / mol). [ka]
[0151] Photoresist preparation. Positive photoresist compositions PR1-PR11 were prepared by dissolving the solid components (copolymer, PAG, quencher, and additives) in a solvent using the materials and amounts shown in Table 2 (in Table 2, the amounts are expressed in weight percent based on 100 weight percent of the total weight of solids). The total solids content of the photoresist compositions was 3.1%. The solvent system contained PGMEA (S1) and 2-hydroxyisobutyric acid methyl ester (S2). Each mixture was shaken in a 100 mL glass container on a mechanical shaker and filtered through a PTFE disk filter with a pore size of 0.20 micrometers.
[0152] [Table 2]
[0153] Lithographic Testing - Examples 1 to 14 E size , EL% and LWR evaluation A 300 mm silicon wafer was spin-coated with AR™ 40A antireflective agent (DuPont Electronics & Industrial) using a cure temperature of 205° C. for 60 seconds to form a first BARC layer with a thickness of 80 nm. The wafer was then spin-coated with AR™ 104 antireflective agent (DuPont Electronics & Industrial) using a cure temperature of 175° C. for 60 seconds to form a second BARC layer with a thickness of 40 nm. The wafer was then spin-coated with the respective photoresist composition from Table 2 and soft-baked at 90° C. for 60 seconds to obtain a photoresist layer with a thickness of 90 nm. The BARC layer and the photoresist layer were coated with a TEL CLEAN TRACK™ LITHIUS™ coating tool. The wafers were exposed to 193 nm activating radiation at various doses using a Nikon S610C immersion scanner (1.30 NA, 0.98 / 0.79 inner / outer sigma, dipole illumination with 35 Y polarization) using a mask with a line-space pattern (line width 38 nm / pitch 80 nm or line width 38 nm / pitch 86 nm). The exposed wafers were post-exposure baked at 95° C. for 60 seconds and developed with 0.26 N tetramethylammonium hydroxide (TMAH) aqueous solution (MF™-CD26, DuPont Electronics & Industrial) for 12 seconds. The wafers were then rinsed with DI water and spun dry to form photoresist patterns. CD linewidth measurements of the formed patterns were performed using a Hitachi High Technologies Co. CG4000 CD-SEM.
[0154] The line-space patterns in nanometers (nm) were analyzed for critical dimensions (CD), where the sizing energy, E size " is the irradiation energy when the CD of the formed line space pattern is equal to the CD of the mask pattern. E size is millijoules per square centimeter (mJ / cm2 The exposure latitude (EL%) is the difference in exposure energy required to print a line-space pattern at ±10% of the target diameter, normalized by the sizing energy. The line width roughness (LWR) is expressed in nanometers (nm) and was determined as the 3 sigma value from the distribution of a total of 100 random points of line width measurements, followed by removing the measurement noise. E size , EL% and LWR data are shown in Tables 3a and 3b.
[0155] E0 Rating A 200 mm silicon wafer was spin-coated with AR™ 40A antireflective agent (DuPont Electronics & Industrial) using a cure temperature of 205° C. for 60 seconds to form a BARC layer with a thickness of 80 nm. The wafer was then spin-coated with each photoresist composition from Table 2 and soft-baked at 90° C. for 60 seconds to obtain a photoresist layer with a thickness of 90 nm. The BARC layer and the photoresist layer were coated with a TEL CLEAN TRACK™ ACT™ 8 coating tool. The wafer was exposed to 193 nm activating radiation at various doses using an ASML 1100 scanner (0.75 NA, 0.89 / 0.64 inner / outer sigma on Quadrapole-30). The exposed wafer was post-exposure baked at 95° C. for 60 seconds and developed with 0.26 N aqueous TMAH solution (MF™-CD26, DuPont Electronics & Industrial) for 60 seconds. The wafer was then rinsed with DI water and spun dry. Film thickness was measured at each exposed area using a KLA Therma-Wave Opti-Probe 7341 and plotted against dose. E values (mJ / cm 2 ) was determined as the first dose value where the remaining film thickness was less than 7% of the original coated thickness. The E0 data are shown in Tables 3a and 3b.
[0156] [Table 3]
[0157] [Table 4]
[0158] Lithographic Testing - Examples 15-30 E size , EL%, LWR and PCM rating A 300 mm silicon wafer was spin coated with AR™ 40A antireflective agent (DuPont Electronics & Industrial) using a cure temperature of 205° C. for 60 seconds to form a first BARC layer with a thickness of 80 nm. The wafer was then spin coated with AR™ 104 antireflective agent (DuPont Electronics & Industrial) using a cure temperature of 175° C. for 60 seconds to form a second BARC layer with a thickness of 40 nm. The wafer was then spin coated with each photoresist composition from Table 2 and soft baked at 90° C. for 60 seconds to obtain a photoresist layer with a thickness of 90 nm. The BARC layer and the photoresist layer were coated with a TEL CLEAN TRACK™ LITHIUS™ coating tool. The wafers were exposed to 193 nm activating radiation at various doses using an ASML 1900i immersion scanner (1.35 NA, 0.988 / 0.90 inner / outer sigma, dipole illumination with 35 Y polarization) using a mask with a 1:1 line-space pattern (line width 38 nm / pitch 76 nm or line width 37 nm / pitch 74 nm). The exposed wafers were post-exposure baked at 95° C. for 60 seconds and developed with 0.26 N tetramethylammonium hydroxide (TMAH) aqueous solution (MF™-CD26, DuPont Electronics & Industrial) for 12 seconds. The wafers were then rinsed with DI water and spun dry to form the photoresist patterns. CD linewidth measurements of the formed patterns were performed using a Hitachi High Technologies Co. CG4000 CD-SEM.
[0159] The line-space patterns in nanometers (nm) were analyzed for critical dimensions (CD), where the sizing energy, E size " is the irradiation energy when the CD of the formed line space pattern is equal to the CD of the mask pattern. E size is millijoules per square centimeter (mJ / cm 2 ) units. Exposure latitude (EL%) is the difference in exposure energy required to print a line-space pattern at ±10% of the target diameter, normalized by the sizing energy. Linewidth roughness (LWR) is expressed in nanometers (nm) and was determined as the 3 sigma value from the distribution of a total of 100 random points of linewidth measurement, followed by removing the measurement noise. PCM is the pattern collapse margin, expressed in nanometers. E size , EL%, LWR and PCM data are shown in Tables 4a and 4b.
[0160] E0 Rating A 200 mm silicon wafer was spin-coated with AR™ 40A antireflective agent (DuPont Electronics & Industrial) using a cure temperature of 205° C. for 60 seconds to form a BARC layer with a thickness of 80 nm. The wafer was then spin-coated with each photoresist composition from Table 2 and soft-baked at 90° C. for 60 seconds to obtain a photoresist layer with a thickness of 90 nm. The BARC layer and the photoresist layer were coated with a TEL CLEAN TRACK™ ACT™ 8 coating tool. The wafer was exposed to 193 nm activating radiation at various doses using an ASML 1100 scanner (0.75 NA, 0.89 / 0.64 inner / outer sigma on Quadrapole-30). The exposed wafer was post-exposure baked at 95° C. for 60 seconds and developed with 0.26 N aqueous TMAH solution (MF™-CD26, DuPont Electronics & Industrial) for 60 seconds. The wafer was then rinsed with DI water and spun dry. Film thickness was measured at each exposed area using a KLA Therma-Wave Opti-Probe 7341 and plotted against dose. E values (mJ / cm 2 ) was determined as the first dose value where the remaining film thickness was less than 7% of the original coated thickness. The E0 data are shown in Tables 4a and 4b.
[0161] [Table 5]
[0162] [Table 6]
[0163] EOMMA / ECPMA / α-GBLMA / aMMBL copolymer synthesis [ka] Triblock copolymer synthesis. (EOMMA / ECPMA / α-GBLMA / aMMBL) Triblock copolymer 9 was prepared as follows: A monomer mixture of 11.5 g α-GBLMA, 12.7 g ECPMA, 7.6 g aMMBL, and 3.2 g EOMMA was prepared. 11.0 g of the monomer mixture was combined with 5.5 g PGMEA and 148 mg V40 initiator to obtain a feed solution. The feed solution was degassed and placed in a syringe before use. 468 mg 2-cyano-2-propyldodecyltrithiocarbonate was used as a chain transfer agent (CTA) in the reactor, protected under N2 at 115°C. 1 / 3 of the feed solution was added to the CTA and heated for 90 minutes, another 1 / 3 of the feed solution was added to the CTA and heated for 90 minutes, then the remainder of the feed solution was added to the CTA and heated for 120 minutes. Aliquots were taken from the reaction mixture under gentle N2 flow as needed. The block copolymers were isolated by precipitation into isopropanol. Conversions were found to reach over 90% at the end of the polymerization of each block.
[0164] Multiblock copolymer synthesis. (EOMMA / ECPMA / α-GBLMA / aMMBL) Multiblock copolymer 10 was prepared as follows: A monomer mixture of 11.5 g α-GBLMA, 12.7 g ECPMA, 7.6 g aMMBL, and 3.2 g EOMMA was prepared. 11.0 g of the monomer mixture was combined with 5.7 g PGMEA and 285 mg V40 initiator to obtain a feed solution. The feed solution was degassed and placed in a syringe before use. 397 mg 2-cyano-2-propyldodecyltrithiocarbonate was used as the CTA in the reactor, protected under N2 at 115°C. Approximately 1 / 9 of the feed solution was added to the CTA and heated for 60 minutes, and this addition was repeated 8 more times with heating between each subsequent addition of the feed solution. Aliquots were taken from the reaction mixture under gentle N2 flow as needed. The block copolymer was isolated by precipitation into isopropanol. Conversion was found to reach over 90% at the end of the polymerization of each block.
[0165] Tetrablock copolymer synthesis. (EOMMA / ECPMA / α-GBLMA / aMMBL) Tetrablock copolymer 11 was prepared by a method similar to that used to prepare copolymers 9 and 10.
[0166] Comparative copolymers. (EOMMA / ECPMA / α-GBLMA / aMMBL) Random copolymer 8 (comparative) was prepared as follows: 6.3 g of monomer mixture (EOMMA / ECPMA / α-GBLMA / aMMBL in a molar ratio of 10 / 30 / 30 / 30) was combined with 8.2 g of PGMEA and 711 mg of V601 initiator, and the mixture was degassed. After heating at 85° C. for 160 minutes, the copolymer was precipitated in isopropanol.
[0167] Block copolymers derived from the monomer combination EOMMA / ECPMA / α-GBLMA / aMMBL (10 / 30 / 30 / 30 molar ratio) and comparative copolymers are summarized in Table 5.
[0168] [Table 7]
[0169] Photoresist preparation. Positive photoresist compositions PR12-PR19 were prepared by dissolving the solid components (copolymer, PAG, quencher, and additives) in a solvent using the materials and amounts shown in Table 6 (in Table 6, the amounts are expressed in weight percent based on 100 weight percent of the total weight of solids). The total solids content of the photoresist compositions was 3.1%. The solvent system contained propylene glycol methyl ether acetate (S1) and 2-hydroxyisobutyric acid methyl ester (S2). Each mixture was shaken in a 100 mL glass container on a mechanical shaker and filtered through a PTFE disk filter with a pore size of 0.20 micrometers.
[0170] [Table 8]
[0171] Lithographic Testing - Examples 31-54 E size , EL%, LWR and PCM rating A 300 mm silicon wafer was spin coated with AR™ 40A antireflective agent (DuPont Electronics & Industrial) using a cure temperature of 205° C. for 60 seconds to form a first BARC layer with a thickness of 80 nm. The wafer was then spin coated with AR™ 104 antireflective agent (DuPont Electronics & Industrial) using a cure temperature of 175° C. for 60 seconds to form a second BARC layer with a thickness of 40 nm. The wafer was then spin coated with each photoresist composition from Table 6 and soft baked at 90° C. for 60 seconds to obtain a photoresist layer with a thickness of 90 nm. The BARC layer and the photoresist layer were coated with a TEL CLEAN TRACK™ LITHIUS™ coating tool. The wafers were exposed to 193 nm activating radiation at various doses using an ASML 1900i immersion scanner (1.35 NA, 0.988 / 0.90 inner / outer sigma, dipole illumination with 35 Y polarization) using a mask with a line-space pattern (line width 38 nm / pitch 76 nm, line width 37 nm / pitch 74 nm, line width 34 nm / pitch 74 nm, or line width 32 nm / pitch 74 nm). The exposed wafers were post-exposure baked at 95° C. for 60 seconds and developed with 0.26 N TMAH aqueous solution (MF™-CD26, DuPont Electronics & Industrial) for 12 seconds. The wafers were then rinsed with DI water and spun dry to form photoresist patterns. CD line width measurements of the formed patterns were performed using a Hitachi High Technologies Co. CG4000 CD-SEM.
[0172] The line-space patterns in nanometers (nm) were analyzed for critical dimensions (CD), where the sizing energy, E size " is the irradiation energy when the CD of the formed line space pattern is equal to the CD of the mask pattern. E sizeis millijoules per square centimeter (mJ / cm 2 ) units. Exposure latitude (EL%) is the difference in exposure energy required to print a line-space pattern at ±10% of the target diameter, normalized by the sizing energy. Linewidth roughness (LWR) is expressed in nanometers (nm) and was determined as the 3 sigma value from the distribution of a total of 100 random points of linewidth measurement, followed by removing the measurement noise. PCM is the pattern collapse margin, expressed in nanometers. E size , EL%, LWR and PCM data are shown in Tables 7a, 7b and 7c.
[0173] [Table 9]
[0174] [Table 10]
[0175] [Table 11]
[0176] Synthesis of IAM / α-GBLMA / HAMA copolymer [ka] Multiblock copolymer synthesis. (IAM / α-GBLMA / HAMA) Multiblock copolymer 12 was prepared as follows: A monomer mixture of 18.3 g IAM, 11.0 g HAMA, 19.3 g α-GBLMA, and 24.5 g PGMEA was prepared. 12.3 g of the monomer solution was combined with 227 mg V40 initiator as the feed solution. The feed solution was degassed and placed in a syringe before use. 353 mg 2-cyano-2-propyldodecyltrithiocarbonate was used as the CTA in the reactor, protected under N2 at 110°C. Approximately 1 / 8 of the feed solution was added to the CTA and heated for 60 minutes, and this addition was repeated 7 more times with heating after each subsequent addition. Aliquots were taken from the reaction mixture under gentle N2 flow as needed. The block copolymer was isolated by precipitation into isopropanol. Conversion was found to reach more than 97% at the end of the polymerization of each block.
[0177] Comparative copolymer. (IAM / α-GBLMA / HAMA) Comparative copolymer 13 was prepared as follows: A monomer solution of 18.3 g IAM, 11.0 g HAMA, 19.3 g α-GBLMA, and 24.5 g PGMEA was prepared. 153 mg 2-cyano-2-propyldodecyl trithiocarbonate was used as the CTA and combined with 7.7 g of the monomer solution, 15.3 g PGMEA, and 1520 mg V40 initiator in a reactor. After degassing, the mixture was heated to 95° C. for 26 hours, cooled to room temperature, and then precipitated into isopropanol.
[0178] Block copolymers derived from the monomer combination IAM / α-GBLMA / HAMA (30 / 50 / 20 molar ratio) and comparative copolymers are summarized in Table 8.
[0179] [Table 12]
[0180] Photoresist preparation Positive photoresist compositions PR20-PR23 were prepared by dissolving the solid components (copolymer, PAG, quencher, and additives) in a solvent using the materials and amounts shown in Table 9 (in Table 9, the amounts are expressed in weight percent based on 100 weight percent of the total weight of solids). The total solids content of the photoresist compositions was 2.9%. The solvent system contained PGMEA (S1) and 2-hydroxyisobutyric acid methyl ester (S2). Each mixture was shaken in a 100 mL glass container on a mechanical shaker and filtered through a PTFE disk filter with a pore size of 0.20 micrometers.
[0181] [Table 13]
[0182] Lithographic Testing - Examples 55-66 E size , EL%, LWR and PCM rating A 300 mm silicon wafer was spin coated with AR™ 40A antireflective agent (DuPont Electronics & Industrial) using a cure temperature of 205° C. for 60 seconds to form a first BARC layer with a thickness of 80 nm. The wafer was then spin coated with AR™ 104 antireflective agent (DuPont Electronics & Industrial) using a cure temperature of 175° C. for 60 seconds to form a second BARC layer with a thickness of 40 nm. The wafer was then spin coated with each photoresist composition from Table 6 and soft baked at 90° C. for 60 seconds to obtain a photoresist layer with a thickness of 90 nm. The BARC layer and the photoresist layer were coated with a TEL CLEAN TRACK™ LITHIUS™ coating tool. The wafers were exposed to 193 nm activating radiation at various doses using an ASML 1900i immersion scanner (1.35 NA, 0.988 / 0.90 inner / outer sigma, dipole illumination with 35 Y polarization) using a mask with a line-space pattern (line width 38 nm / pitch 76 nm, line width 37 nm / pitch 74 nm, line width 34 nm / pitch 74 nm, or line width 32 nm / pitch 74 nm). The exposed wafers were post-exposure baked at 95° C. for 60 seconds and developed with 0.26 N TMAH aqueous solution (MF™-CD26, DuPont Electronics & Industrial) for 12 seconds. The wafers were then rinsed with DI water and spun dry to form photoresist patterns. CD line width measurements of the formed patterns were performed using a Hitachi High Technologies Co. CG4000 CD-SEM.
[0183] The line-space patterns in nanometers (nm) were analyzed for critical dimensions (CD), where the sizing energy, E size " is the irradiation energy when the CD of the formed line space pattern is equal to the CD of the mask pattern. E size is millijoules per square centimeter (mJ / cm 2) units. Exposure latitude (EL%) is the difference in exposure energy required to print a line-space pattern at ±10% of the target diameter, normalized by the sizing energy. Linewidth roughness (LWR) is expressed in nanometers (nm) and was determined as the 3 sigma value from the distribution of a total of 100 random points of linewidth measurement, followed by removing the measurement noise. PCM is the pattern collapse margin, expressed in nanometers. E size , EL%, LWR and PCM data are shown in Tables 10a, 10b and 10c.
[0184] [Table 14]
[0185] [Table 15]
[0186] [Table 16]
[0187] CHOMMA / α-GBLMA / NLMA copolymer synthesis [ka] Triblock copolymer synthesis. (CHOMMA / α-GBLMA / NLMA) Triblock copolymer 14 was prepared as follows: A monomer solution of 9.5 g α-GBLMA, 11.1 g CHOMMA, and 6.2 g NLMA was prepared in 17.9 g 1,4-dioxane. 10.0 g of the monomer solution was mixed with 82 mg V601 initiator as the feed solution. The feed solution was degassed and placed in a syringe before use. 247 mg 2-cyano-2-propyldodecyltrithiocarbonate was used as the CTA in the reactor, protected under N2 at 85°C. 1 / 3 of the feed solution was added to the CTA and heated for 120 minutes, another 1 / 3 of the feed solution was added to the reactor and heated to 85°C for another 120 minutes, and the remainder of the feed solution was added to the reactor at 85°C and allowed to react for 150 minutes. Aliquots were taken from the reaction mixture under gentle N2 flow as needed. The conversion was found to be greater than 97%. The reaction mixture was diluted with PGMEA and precipitated in isopropanol.
[0188] Tetrablock copolymer synthesis. (CHOMMA / α-GBLMA / NLMA) Multiblock copolymer 15 was prepared using a procedure similar to that used to prepare copolymer 14.
[0189] Comparative copolymers. (CHOMMA / α-GBLMA / NLMA) Random copolymer 16 (comparative) was prepared following a similar procedure as for copolymer 8, using a monomer molar ratio of 40 / 40 / 20.
[0190] Block copolymers derived from the monomer combination CHOMMA / α-GBLMA / NLMA (40 / 40 / 20 molar ratio) and comparative copolymers are summarized in Table 11.
[0191] [Table 17]
[0192] Photoresist preparation Positive photoresist compositions PR24-PR29 were prepared by dissolving the solid components (copolymer, PAG, quencher, and additives) in a solvent using the materials and amounts shown in Table 12 (in Table 12, the amounts are expressed in weight percent based on 100 weight percent of the total weight of solids). The total solids content of the photoresist compositions was 2.9%. The solvent system contained PGMEA (S1) and 2-hydroxyisobutyric acid methyl ester (S2). Each mixture was shaken in a 100 mL glass container on a mechanical shaker and filtered through a PTFE disk filter with a pore size of 0.20 micrometers.
[0193] [Table 18]
[0194] Lithographic Testing - Examples 67-91 E size , EL%, LWR and PCM rating A 300 mm silicon wafer was spin coated with AR™ 40A antireflective agent (DuPont Electronics & Industrial) using a cure temperature of 205° C. for 60 seconds to form a first BARC layer with a thickness of 80 nm. The wafer was then spin coated with AR™ 104 antireflective agent (DuPont Electronics & Industrial) using a cure temperature of 175° C. for 60 seconds to form a second BARC layer with a thickness of 40 nm. The wafer was then spin coated with each photoresist composition from Table 12 and soft baked at 90° C. for 60 seconds to obtain a photoresist layer with a thickness of 90 nm. The BARC layer and the photoresist layer were coated with a TEL CLEAN TRACK™ LITHIUS™ coating tool. The wafers were exposed to 193 nm activating radiation at various doses using an ASML 1900i immersion scanner (1.35 NA, 0.988 / 0.90 inner / outer sigma, dipole illumination with 35 Y polarization) using a mask with a line-space pattern (line width 38 nm / pitch 76 nm, line width 37 nm / pitch 74 nm, line width 34 nm / pitch 74 nm, or line width 32 nm / pitch 74 nm). The exposed wafers were post-exposure baked at 95° C. for 60 seconds and developed with 0.26 N TMAH aqueous solution (MF™-CD26, DuPont Electronics & Industrial) for 12 seconds. The wafers were then rinsed with DI water and spun dry to form photoresist patterns. CD line width measurements of the formed patterns were performed using a Hitachi High Technologies Co. CG4000 CD-SEM.
[0195] The line-space patterns in nanometers (nm) were analyzed for critical dimensions (CD), where the sizing energy, E size " is the irradiation energy when the CD of the formed line space pattern is equal to the CD of the mask pattern. E size is millijoules per square centimeter (mJ / cm 2) units. Exposure latitude (EL%) is the difference in exposure energy required to print a line-space pattern at ±10% of the target diameter, normalized by the sizing energy. Linewidth roughness (LWR) is expressed in nanometers (nm) and was determined as the 3 sigma value from the distribution of a total of 100 random points of linewidth measurement, followed by removing the measurement noise. PCM is the pattern collapse margin, expressed in nanometers. E size , EL%, LWR and PCM data are shown in Tables 13a, 13b and 13c.
[0196] [Table 19]
[0197] [Table 20]
[0198] [Table 21]
[0199] [Table 22]
[0200] While the present disclosure has been described in connection with what are presently considered to be practical exemplary embodiments, it is to be understood that the invention is not limited to the disclosed embodiments, but rather is intended to cover various modifications and equivalent arrangements included within the spirit and scope of the appended claims.
Claims
1. a first block comprising two or more structurally distinct repeat units; A second block comprising two or more structurally distinct repeat units. A block copolymer comprising: the repeat unit of the first block comprises an acid labile group, a lactone group, a salt group, or a hydroxyaryl group; and the repeat unit of the second block comprises an acid labile group, a lactone group, a salt group, or a hydroxyaryl group; The two or more structurally distinct repeat units of the first block are the same as the two or more structurally distinct repeat units of the second block.
2. 2. The block copolymer of claim 1, wherein the two or more structurally distinct repeat units of the first block and the two or more structurally distinct repeat units of the second block are present in the first block and the second block in substantially the same ratio, and each block has the same structural unit gradient direction from the first end to the second end of the block.
3. 3. The block copolymer of claim 1 or 2, wherein the first block and the second block each comprise a repeat unit that comprises an acid labile group.
4. The block copolymer of any one of claims 1 to 3, wherein the first block and the second block each comprise a repeat unit that comprises a lactone group or a salt group.
5. The block copolymer according to any one of claims 1 to 4, wherein the average number of repeat units in each block is 5 or more.
6. The block copolymer according to any one of claims 1 to 5, wherein the average number of blocks in the block copolymer is from 3 to 10.
7. 7. The block copolymer of claim 1, further comprising a block that does not have the same structurally distinct repeat units as the first block and the second block.
8. A polymer comprising one or more block copolymers according to any one of claims 1 to 7 attached to another moiety of the polymer.
9. A photoresist composition comprising the block copolymer according to any one of claims 1 to 8 and a solvent.
10. A pattern formation method comprising the steps of: forming a photoresist composition layer on a substrate from the photoresist composition of claim 9; patternwise exposing the photoresist composition layer to activating radiation; developing the exposed photoresist composition layer to provide a resist relief image. A pattern forming method comprising the steps of:
Citation Information
Patent Citations
Hair-cosmetic composition comprising at least one film-forming gradient copolymer, aerosol composition comprising the cosmetic composition and method for treating hair using the composition
US20040180019A1
Radiation-sensitive copying composition
US4189323A
Processes based on atom (or group) transfer radical polymerization and novel (co)polymers having useful structures and properties
US6887962B2
Compound, resin, resist composition and method for producing resist pattern
US8431325B2